White UV-absorbing surface-reacted calcium carbonate doped with titanium species

By treating calcium carbonate in aqueous medium and doping titanium substances, a high surface area white absorbing UV-surface reaction titanium carbonate substance is prepared, which solves the carcinogenicity and dust floating problems of submicron or nano titanium dioxide, and achieves a safe and economical multi-purpose Use product.

CN119213085APending Publication Date: 2024-12-27OMYA INT AG
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
CN202380041340.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-25
Filing Date
2023-05-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, titanium dioxide powder containing submicron or nanometer size is restricted in food and cosmetics due to potential carcinogenicity and dust problems. At the same time, surface-reacted calcium carbonate and titanium dioxide are easily mixed in dry form and particles are easily separated and Health risks.

Method used

By using H3O+ ion donors to treat the calcium carbonate material in an aqueous medium, the surface-reacted calcium carbonate is formed, and the structure of titanium substances are doped with titanium substances, titanium carbonate substances with high surface area and white absorption UV characteristics are prepared, avoiding the Titanium dioxide in powder form is used and improves product handling and transportation safety.

Benefits of technology

Achieve the preparation of titanium-doped surface-reactive calcium carbonate that is easy to handle, safe, and affordable, white UV absorbing, suitable for a variety of applications, including paint, paper, catalytic and sunscreen without the need to mark submicron or nano-size titanium dioxide has increased consumer acceptance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213085A_ABST
    Figure CN119213085A_ABST
Patent Text Reader

Abstract

The invention relates to a white UV-absorbing surface-reacted calcium carbonate doped with titanium species, comprising calcite and hydroxyapatite in a weight ratio of 99: 1 to 1: 99, based on the dry weight of calcite and hydroxyapatite, and having a specific surface area of 15 m2 / g to 200 m2 / g, the titanium species being present in an amount of 0.01 to 20 wt% of the titanium element, based on the total dry weight of the surface-reacted calcium carbonate. Furthermore, the present invention relates to a method for producing a white UV-absorbing surface-reacted calcium carbonate doped with a titanium species, to the use of said white UV-absorbing surface-reacted calcium carbonate doped with a titanium species, and to an article comprising said white UV-absorbing surface-reacted calcium carbonate doped with a titanium species.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a white, UV-absorbing, surface-reacted calcium carbonate doped with a titanium substance, comprising calcite and hydroxyapatite in a weight ratio of 99:1 to 1:99 based on the dry weight of calcite and the dry weight of hydroxyapatite and having a surface reaction of 15 m 2 / g-200m 2 / g specific surface area, wherein the titanium substance is present in an amount of 0.01-20 wt. % titanium element, based on the total dry weight of the surface-reacted calcium carbonate. In addition, the present invention relates to a method for producing a white UV-absorbing surface-reacted calcium carbonate doped with a titanium substance, the use of the white UV-absorbing surface-reacted calcium carbonate doped with a titanium substance, and an article comprising the white UV-absorbing surface-reacted calcium carbonate doped with a titanium substance. Background Art

[0002] Mineral fillers, and especially those containing calcium carbonate, are often used as particulate fillers added to resins or adhesives, paints or papers and can improve specific properties such as opacity, brightness, stability, viscosity, strength or stiffness and can make the product cheaper, or a mixture of both.

[0003] EP2997833 relates to the use of surface-reacted calcium carbonate as an anti-caking agent, wherein the surface-reacted calcium carbonate is the reaction product of natural ground or precipitated calcium carbonate with carbon dioxide and at least one acid in an aqueous medium, wherein the at least one acid is selected from hydrochloric acid, sulfuric acid, sulfurous acid, phosphoric acid, citric acid, oxalic acid, acetic acid, formic acid and mixtures thereof, wherein the carbon dioxide is generated in situ by acid treatment and / or supplied from an external source, and wherein the surface-reacted calcium carbonate particles have a volume median particle size d of 0.1-50 mm. 50 .

[0004] EP2926797 relates to an oral care composition for tooth remineralization and / or whitening comprising surface-reacted calcium carbonate, wherein the surface-reacted calcium carbonate is the reaction product of natural or synthetic calcium carbonate with carbon dioxide and at least one acid.

[0005] EP20186219.0 relates to a curable fluoropolymer composition comprising a crosslinkable fluoropolymer and surface-reacted calcium carbonate as filler.

[0006] In addition to this, additional pigments and particles are usually added, which add further advantageous features to the filler composition. Pigments or particles are generally known as materials that change the color of reflected or transmitted light due to wavelength selective absorption. This physical process is different from fluorescence, phosphorescence and other forms of luminescence, in which the material emits light. Pigments are used for coloring, such as paints, inks, plastics, fabrics, cosmetics, foods and other materials. Most of the pigments used are dry colorants, usually ground into fine powders.

[0007] White pigments occupy a special place in the pigment world due to their industrial relevance. For example, the European paper industry uses more than 10 million tons of white pigments every year. White pigments are also used in paints and coatings. Especially in the manufacture of dispersion paints, white pigments are the base color of the coloring system.

[0008] A known white pigment is titanium dioxide, also known as titanium white, pigment white 6 (PW6), CI 77891 or E number E171. Typically, it is derived from ilmenite, rutile, and anatase or mixtures thereof. It has a wide range of applications, especially as a white pigment in paper and plastic materials and paints. In addition, due to its white color, it is also used as food coloring or cosmetic applications. In addition, titanium dioxide is able to absorb ultraviolet rays and is therefore often used in sunscreens and sunscreen applications.

[0009] EP0634462 relates to a coating composition containing very finely divided TiO2, comprising 0.5-30.0% by volume of color pigments and / or carbon black, 55.0-98.5% by volume of binder solids and 0.3-15.0% by volume of very finely divided TiO2, whose particle size is 5-40 nm and has high total reflectivity (brightness) and strong color depth.

[0010] EP2188125 relates to a self-cleaning, defouling paint comprising: about 5% to about 40% by volume of photocatalytic titanium dioxide in substantially pure anatase form, the photocatalytic titanium dioxide being characterized by an average crystallite size between about 5 nm and about 30 nm and being photocatalytically active in the presence of visible light; one or more additional pigments, and a styrene acrylic copolymer binder.

[0011] US7476704 relates to a polymer composition comprising a polymer resin, a flash calcined kaolin clay filler and a titanium dioxide filler. The titanium dioxide has an average aggregate size in the range of about 0.2-0.35 μm.

[0012] AU630406 relates to titanium dioxide particles having an average primary particle size of less than 100 nm, each of which is substantially coated with a phospholipid. The phospholipid-coated titanium dioxide particles can be incorporated into oil-in-water and water-in-oil emulsions to provide novel sunscreen compositions having excellent UV shielding efficiency, long-term stability and water resistance properties.

[0013] EP 3360601 relates to a cosmetic composition with UV-A and / or UV-B protection, comprising at least one inorganic UV filter and a composition having a volume median particle size d 50 Surface-reacted calcium carbonate with a diameter of 0.1-90 μm, wherein the surface-reacted calcium carbonate is natural ground calcium carbonate or precipitated calcium carbonate with carbon dioxide and one or more H3O + The reaction product of the ion donor, wherein the carbon dioxide is composed of H3O + The ion donor treatment is formed in situ and / or supplied from an external source.However, in this patent application only a mixture of inorganic UV filters and surface-reacted calcium carbonate is provided, but the structure of the surface-reacted calcium carbonate is not modified.

[0014] EP3517176 relates to a particle having a volume median particle size d 50 Use of surface-reacted calcium carbonate with a diameter of 0.1 to 90 μm as a skin appearance regulator in cosmetic and / or skin care compositions, wherein the surface-reacted calcium carbonate is natural ground calcium carbonate or precipitated calcium carbonate with carbon dioxide and one or more H3O + The reaction product of the ion donor, wherein the carbon dioxide is composed of H3O + The ion donor is formed in situ and / or supplied from an external source. EP3517178 relates to the use of surface-reacted calcium carbonate as an agent for modifying the biomechanical properties of the skin in a cosmetic and / or skin care composition, wherein the surface-reacted calcium carbonate has a volume median particle size d 50 0.1-90 μm, and wherein the surface-reacted calcium carbonate is natural ground calcium carbonate or precipitated calcium carbonate with carbon dioxide and one or more H3O + The reaction product of the ion donor, wherein the carbon dioxide is composed of H3O + The ion donor treatment is formed in situ and / or supplied by an external source. The cosmetic and / or skin care composition may contain further additives, such as inorganic UV filters, for example titanium dioxide. However, these documents also only relate to mixtures of inorganic UV filters and surface-reacted calcium carbonate, but do not modify the structure of the surface-reacted calcium carbonate.

[0015] However, in some applications, titanium dioxide is used in the form of a powder containing submicron or nanometer sized titanium dioxide particles. This is disadvantageous because submicron and / or nanometer sized TiO2 powders are problematic due to the potential carcinogenicity of such small titanium dioxide particles. Due to this potential carcinogenicity, the European Union is attempting to ban such particles at least in food and cosmetic applications.

[0016] Another disadvantage is that when the two compounds (surface-reacted calcium carbonate and titanium dioxide) are mixed in the form of a dry product, this can lead to airborne dust, which can cause health problems, especially when inhaled. In addition, when the two compounds (surface-reacted calcium carbonate and titanium-containing material (e.g. titanium dioxide) are mixed in the form of a dry product, particle separation often occurs during transportation due to PSD (particle size distribution) and density differences.

[0017] In view of the above, there is a continuing need for particles or fillers comprising surface-reacted calcium carbonate and titanium species and having excellent properties in terms of their color, their UV absorbance and in terms of their mechanical and particle properties.

[0018] It is therefore an object of the present invention to provide an improved filler or improved particles comprising surface-reacted calcium carbonate and useful in polymer applications, paper coating applications, papermaking, especially in the manufacture of decorative paper, paints, coatings, sealants, adhesives, feed, pharmaceuticals, concrete, cement, cosmetics, water treatment, engineered wood applications, gypsum board applications, packaging applications, catalysis, gas treatment applications and / or agricultural applications. The filler or particles should have a white appearance so that they are particularly useful in paints and paper without adding unwanted color to such applications.

[0019] Furthermore, it is desirable to provide fillers or particles which have UV absorbing properties and can be used in medicine or cosmetics, especially in sunscreens and sun protection applications. The fillers or particles should be non-toxic to humans, have no harmful effects on the environment, and can be used in cosmetic applications. In particular, the fillers or particles should be free of titanium dioxide in the submicron and / or nanometer size range in order to avoid health problems, especially the carcinogenicity of such products.

[0020] Furthermore, it is desirable that the titanium species cannot be separated from the surface-reacted calcium carbonate simply by washing or in a liquid composition.

[0021] A further object of the invention was that the filler or granulate should be easy and quick to produce, affordable and, above all, easy to handle. Summary of the invention

[0022] The foregoing and other objects are solved by the subject matter as defined in the independent claims.

[0023] According to one aspect of the present invention, there is provided a method for producing white UV absorbing surface-reacted calcium carbonate doped with titanium species, comprising the following steps:

[0024] a) providing a material comprising calcium carbonate,

[0025] b) Provide at least one H3O + ion donor,

[0026] c) providing at least one substance comprising titanium, and

[0027] d) treating in an aqueous medium with at least one H3O + treating the calcium carbonate-containing material of step a) with an ion donor to form an aqueous suspension of surface-reacted calcium carbonate, and

[0028] The at least one titanium-containing substance of step c) is added before and / or during and / or after step d).

[0029] According to another aspect of the present invention, there is provided a white UV absorbing surface-reacted calcium carbonate doped with titanium species, comprising calcite and hydroxyapatite and having a specific surface area of ​​15 m 2 / g-200m 2 / g, which is measured using nitrogen and the BET method according to ISO9277:2010,

[0030] wherein the weight ratio of calcite to hydroxyapatite is 99:1 to 1:99, based on the dry weight of calcite and the dry weight of hydroxyapatite, and

[0031] The titanium material is present in an amount of 0.01-20 wt % titanium element, based on the total dry weight of the surface-reacted calcium carbonate.

[0032] The inventors surprisingly found that surface-reacted calcium carbonate particles doped with titanium substances can be prepared by the method of the present invention. The method for producing these particles is an easy and fast method, and the product obtained is reasonably priced and especially easy to handle. The method can be carried out in standard equipment without causing significant burdens on humans and the environment. Such methods and products are advantageous because the final consumer does not have to handle particles containing titanium dioxide in powder form, and the powder contains submicron or nanometer-sized titanium dioxide particles. On the contrary, the particles obtained contain the advantageous properties of surface-reacted calcium carbonate, and especially have a high surface area and are also white and UV-absorbing. The white UV-absorbing calcium carbonate doped with titanium substances obtained can be used for a variety of applications, such as paints, paper, coatings, catalysis or sunscreens. Such products do not have to be labeled as titanium dioxide particles in the submicron and / or nanometer size range in the ingredient list, and therefore should have a higher acceptance of the final consumer.

[0033] According to another aspect of the present invention, the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species according to the present invention is used in polymer applications, paper coating applications, papermaking, in particular in the manufacture of decorative paper, paints, coatings, sealants, adhesives, feed, pharmaceuticals, concrete, cement, cosmetics, water treatment, engineered wood applications, gypsum board applications, packaging applications, catalysis, gas treatment applications and / or agricultural applications.

[0034] According to a further aspect of the invention, the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium substances according to the invention is used for sun protection of plants and parts thereof or for chemical and physical sun protection in cosmetic preparations.

[0035] According to another aspect of the present invention, there is provided an article comprising the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species according to the present invention, wherein the article is selected from paper products, engineered wood products, gypsum board products, polymer products, hygiene products, medical products, health products, filtration products, woven materials, non-woven materials, geotextile products, agricultural products, horticultural products, clothing, footwear products, luggage products, household products, industrial products, packaging products, building products and construction products.

[0036] Advantageous embodiments of the above aspects are defined in the respective dependent claims.

[0037] According to one embodiment of the present invention, the material comprising calcium carbonate is natural ground calcium carbonate and / or precipitated calcium carbonate, preferably natural ground calcium carbonate is selected from marble, chalk, limestone and mixtures thereof, and / or the precipitated calcium carbonate is selected from precipitated calcium carbonate having aragonite, vaterite or calcite crystal form and mixtures thereof.

[0038] According to another embodiment of the present invention, the calcium carbonate containing material is in the form of particles having a weight median particle size d of 0.05-10 μm, preferably 0.2-5.0 μm, more preferably 0.4-3.0 μm and most preferably 0.6-1.2 μm. 50 (weight), and / or a weight topcut particle size d of 0.15-55 μm, preferably 1-40 μm, more preferably 2-25 μm and most preferably 3-15 μm 98 (weight).

[0039] According to another embodiment of the present invention, at least one H3O + The ion donor is selected from phosphoric acid, citric acid, acid salts, tartaric acid and mixtures thereof, preferably at least one H3O + The ion donor is selected from phosphoric acid, H2PO4 - (Selected from Li +、Na + and / or K + The cations are at least partially neutralized), HPO4 2- (Selected from Li + 、Na + , K + Mg 2+ and / or Ca 2+ cations at least partially neutralized), citric acid, and mixtures thereof, more preferably at least one H3O + The ion donor is selected from phosphoric acid, citric acid or a mixture thereof, and most preferably at least one H3O + The ion donor is phosphoric acid.

[0040] According to another embodiment of the present invention, at least one H3O + The molar ratio of ion donor to calcium carbonate containing material is 0.01-4, preferably 0.02-2, more preferably 0.05-1 and most preferably 0.1-0.58.

[0041] According to another embodiment of the present invention, at least one substance containing titanium is selected from titanium salts, titanium hydroxide, titanium oxide and mixtures thereof, preferably the substance containing titanium is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the substance containing titanium is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof.

[0042] According to another embodiment of the present invention, the at least one substance comprising titanium is provided in an amount of 0.1-20 wt. % titanium element, preferably 0.5-15 wt. %, more preferably 1.0-10 wt. % and most preferably 2.5-7.5 wt. %, based on the total dry weight of the material comprising calcium carbonate.

[0043] According to another embodiment of the present invention, in step d), at least one H3O + The material comprising calcium carbonate is treated with a solution of an ion donor and at least one substance comprising titanium of step c).

[0044] According to another embodiment of the present invention, in step d), the pH value of the obtained aqueous suspension of surface-reacted calcium carbonate is 4.5-11, preferably 5.5-10 and most preferably 6.0-8.0.

[0045] According to another embodiment of the present invention, step d) is carried out at a temperature of 20-95°C, preferably 30-85°C, more preferably 40-80°C, even more preferably 50-75°C and most preferably 65-73°C.

[0046] According to another embodiment of the present invention, the method further comprises a step e) of separating the white UV absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step d), and preferably step e) is accomplished by solvent evaporation and / or filter pressing and / or

[0047] The method further comprises the step f): drying the surface-reacted calcium carbonate doped with titanium species at a temperature in the range of 60-600° C., preferably 80-450° C., most preferably 95-400° C. after step d) or after step e) (if present), preferably until the moisture content of the surface-reacted calcium carbonate doped with titanium species is between 0.01 and 5 wt.-%, based on the total weight of the dried surface-reacted calcium carbonate.

[0048] According to another embodiment of the present invention, the surface-reacted calcium carbonate doped with titanium species has

[0049] (i)25m 2 / g-180m 2 / g, more preferably 30m 2 / g-160m 2 / g, even more preferably 45m 2 / g-150m 2 / g, most preferably 50m 2 / g-140m 2 Specific surface area of ​​100 g / m, measured using nitrogen and the BET method according to ISO 9277:2010, and / or

[0050] (ii) a volume-determined median particle size d of 1-100 μm, preferably 2-60 μm, more preferably 3-40 μm, even more preferably 4-30 μm and most preferably 5-15 μm 50 (volume), and / or

[0051] (iii) a volume-determined top cut particle size d of 2-150 μm, preferably 4-100 μm, more preferably 6-80 μm, even more preferably 8-60 μm and most preferably 10-30 μm 98 (volume), and / or

[0052] (iv) 0.1-2.3 cm 3 / g, preferably 0.2-2.0cm 3 / g, more preferably 0.4-1.8cm 3 / g and most preferably 0.6-1.6cm 3 The intrusion specific pore volume in the particle range of / g was calculated from the results of mercury porosimetry measurements.

[0053] According to another embodiment of the present invention, the weight ratio of calcite to hydroxyapatite in the surface-reacted calcium carbonate doped with titanium species is 80:20-20:80, based on the dry weight of calcite and the dry weight of hydroxyapatite, preferably 70:30-30:70 and most preferably 60:40-40:60 and / or the titanium species is present in an amount of 0.05-15 wt% titanium element, preferably 0.1-10 wt% and most preferably 0.5-5 wt%, based on the total dry weight of the surface-reacted calcium carbonate.

[0054] It should be understood that for the purposes of the present invention, the following terms have the following meanings:

[0055] "White" pigments or "white" particles or "white" filler materials within the meaning of the present invention are solid inorganic coloring materials with a defined chemical composition and characteristic crystalline structure. Such materials are insoluble in water and therefore result in suspensions when in contact with water. They have a white appearance when irradiated with daylight.

[0056] "UV-absorbing" pigments or particles in the meaning of the present invention absorb at least some of the ultraviolet B (UV-B) radiation in the range of 280-320 nm and the ultraviolet A (UV-A) radiation in the range of >320 to 400 nm.

[0057] "Surface-reacted calcium carbonate" within the meaning of the present invention is natural ground calcium carbonate or precipitated calcium carbonate reacted with one or more H3O + In the context of the present invention, "H3O + The "ion donor" is a Bronsted acid and / or acid salt.

[0058] A "calcium carbonate-containing material" in the meaning of the present invention is a mineral material or synthetic material having a calcium carbonate content of at least 80% by weight, preferably 85% by weight, more preferably 90% by weight and most preferably 95% by weight, based on the total weight of the calcium carbonate-containing material.

[0059] "Natural ground calcium carbonate" (GCC also referred to as GNCC) in the meaning of the present invention is calcium carbonate obtained from natural sources such as limestone, marble, or chalk and processed by wet and / or dry treatments such as grinding, screening and / or classification (e.g. by cyclones or classifiers).

[0060] "Precipitated calcium carbonate" (PCC) in the meaning of the present invention is a synthetic material, obtained by precipitation after reaction of carbon dioxide and lime in an aqueous, semi-dry or humid environment or by precipitation of calcium and carbonate sources in water. PCC can be vaterite, calcite or aragonite crystalline form. PCC is described, for example, in EP2447213 A1, EP2524898 A1, EP2371766 A1, EP1712597A1, EP1712523A1 or WO2013142473A1.

[0061] A "substance comprising titanium" within the meaning of the present invention is a substance comprising titanium in ionic form or in covalently bonded form having an oxidation number other than zero.

[0062] "Doping" the surface-reacted calcium carbonate with a titanium species refers to a surface-reacted calcium carbonate wherein a titanium species is introduced into the structure of the surface-reacted calcium carbonate. Titanium species refers to titanium having an oxidation number other than zero.

[0063] The "particle size" of particulate materials other than surface-reacted calcium carbonate (e.g., GCC or PCC) is defined herein by the particle size d x (weight) distribution description. Among them, the value d x (by weight) represents the diameter such that x weight % of the particles have a diameter smaller than d x (weight). This means that for example d 20 The (weight) value is the particle size below which 20% by weight of all particles are smaller. 50 The (weight) value is therefore the weight median particle size, ie the particle size below which 50% by weight of all particles are smaller, and d 98 The (weight) value (called weight-based top cut) is the particle size below which 98% by weight of all particles are smaller. The weight-based median particle size d is measured by the sedimentation method. 50 (weight) and top cut d 98 (weight), the sedimentation method is the analysis of sedimentation behavior in a gravitational field. The measurement was performed using a Sedigraph from Micromeritics Instrument Corporation, USA TM 5120. The method and the instrument are known to the skilled person and are commonly used for determining the particle size distribution. The measurement is carried out in a 0.1 wt. % Na4P2O7 aqueous solution. A high-speed stirrer and sonication are used to disperse the sample.

[0064] The "particle size" of the surface-reacted calcium carbonate is described herein as the particle size distribution based on volume. x (volume). Where, the value d x (volume) represents the diameter such that x volume % of the particles have a diameter smaller than dx The diameter of a volume. This means that, for example, d 20 The (volume) value is the particle size below which 20% by volume of all particles are smaller. 50 The (volume) value is therefore the volume median particle size, ie the particle size below which 50% by volume of all particles are smaller, and d 98 The (volume) value (called the volume-based top cut) is the particle size below which 98% by volume of all particles are smaller. The volume median particle size d is estimated using a Malvern Mastersizer 3000 laser diffraction system. 50 The d was measured using a Malvern Mastersizer 3000 laser diffraction system. 50 or 98 The value indicates the diameter value such that 50% or 98% of the particles by volume, respectively, have a diameter smaller than this value. The raw data obtained by the measurement were analyzed using Mie theory, with the particle refractive index being 1.57 and the absorptivity being 0.005.

[0065] For the purposes of the present invention, "porosity" or "pore volume" refers to the intrusion specific pore volume within a particle. In the context of the present invention, the term "pores" is understood to describe the spaces found between and / or within particles, i.e., which are formed by particles when they are packed together in nearest neighbor contact (inter-particle pores), such as in powders or compacts, and / or the void spaces within porous particles (intra-particle pores), and which when saturated with liquid allow the passage of liquid under pressure and / or support the absorption of surface wetting liquids.

[0066] Results measured using mercury intrusion porosimetry The specific pore volume was measured using a Micromeritics Autopore V 9620 mercury intrusion porosimeter with a maximum applied pressure of 414 MPa (60,000 psi) of mercury equivalent to a Laplace throat of 0.004 μm. The equilibrium time used in each pressure step was 20 s. The sample material was sealed in a 3 cm 3The data were corrected for mercury compression, penetrometer expansion, and elastic compression of the sample material using the software Pore-Comp (Gane, PAC, Kettle, JP, Matthews, GP, and Ridgway, CJ, "Void Space Structure of Compressible Polymer Spheres and Consolidated Calcium Carbonate Paper-Coating Formulations", Industrial and Engineering Chemistry Research, 1996, 35 (5), 1996, pp. 1753-1764).

[0067] The total pore volume seen in the cumulative inflection data is broken down into two regions where the intrusion data drops from 214 μm to about 1 to 4 μm, showing coarse packing of the sample between any strongly contributing aggregate structures. Below these diameters is fine inter-particle packing of the particles themselves. If they also have intra-particle pores, this region appears bimodal, and by taking the specific pore volume in pores where the mercury intrusion is finer than the modal turning point (i.e. finer than the bimodal point of inflection), we therefore define the intra-particle specific pore volume. The sum of these three regions yields the overall total pore volume of the powder, but is strongly dependent on the original sample compaction / sedimentation of the powder at the coarse pore end of the distribution.

[0068] By taking the first derivative of the cumulative intrusion curve, the pore size distribution based on the equivalent Laplace diameter is revealed, which inevitably includes pore shielding. The differential curve clearly shows the coarse aggregate pore structure region, the inter-particle pore region, and the intra-particle pore region (if any). Knowing the intra-particle pore diameter range, the remaining inter-particle and inter-aggregate pore volume can be subtracted from the total pore volume to provide the required individual pore volume of the inner pore based on the pore volume per unit mass (specific pore volume). Of course, the same subtraction principle applies to isolate any other pore size region of interest.

[0069] Throughout this document, the term "specific surface area" (in m 2 The specific surface area in m2 / g (which is used to define the functionalized calcium carbonate or other material) refers to the specific surface area as determined by using the BET method (using nitrogen as the adsorption gas). Throughout this document, the specific surface area (in m2) is determined using the BET method (using nitrogen as the adsorption gas) known to the skilled person (ISO 9277:2010). 2The total surface area of ​​the filler material (in m2) is then obtained by multiplying the mass (in g) of the corresponding sample by the specific surface area. 2 count).

[0070] For the purposes of this application, a "water-insoluble" material is defined as a material that, when 100 g of said material is mixed with 100 g of deionized water and filtered on a filter having a pore size of 0.2 μm at 20° C. to recover a liquid filtrate, provides less than or equal to 1 g of recovered solid material after evaporation of 100 g of said liquid filtrate at 95 to 100° C. at ambient pressure. A "water-soluble" material is defined as a material that, when 100 g of said material is mixed with 100 g of deionized water and filtered on a filter having a pore size of 0.2 μm at 20° C. to recover a liquid filtrate, provides greater than 1 g of recovered solid material after evaporation of 100 g of said liquid filtrate at 95 to 100° C. at ambient pressure.

[0071] For the purposes of the present invention, the "solids content" of a liquid composition is a measure of the amount of material remaining after evaporation of all solvent or water. If necessary, the "solids content" of a suspension given in % by weight within the meaning of the present invention can be determined using a Moisture Analyzer HR73 from Mettler-Toledo (T = 120 ° C, automatic switch off 3, standard drying) with a sample size of 5 to 20 g.

[0072] Unless otherwise specified, the term "drying" means removing at least a portion of the water from the material to be dried, according to the following method, so that a constant weight of the "dried" material obtained is reached at 220°C. The term "dry" material or "dry" composition is to be understood as a material / composition having less than 1.0% by weight of water relative to the weight of the material / composition. The % water (equal to the residual total moisture content) is determined according to the Coulometric Karl Fischer measurement method, wherein the material / composition is heated to 220°C and the water content released as vapor and separated using a nitrogen flow (at 100 ml / min) is determined in a Coulometric Karl Fischer apparatus.

[0073] For the purposes of the present invention, the term "viscosity" or "Brookfield viscosity" refers to Brookfield viscosity. Brookfield viscosity is measured at 100 rpm using a suitable axis of a Brookfield RV-axis set at 25 ° C ± 1 ° C by a Brookfield DV-II + Pro viscometer for this purpose and is specified in mPa s. Based on the technical knowledge of the technician, he will select an axis suitable for the viscosity range to be measured from the Brookfield RV-axis set. For example, for the viscosity range between 200 and 800 mPa s, axis number 3 can be used, for the viscosity range between 400 and 1600 mPa s, axis number 4 can be used, for the viscosity range between 800 and 3200 mPa s, axis number 5 can be used, for the viscosity range between 1000 and 2000000 mPa s, axis number 6 can be used, and for the viscosity range between 4000 and 8000000 mPa s, axis number 7 can be used.

[0074] A "suspension" or "slurry" within the meaning of the present invention comprises undissolved solids and water, and optionally further additives, and generally contains a large amount of solids and may therefore have a higher density and be more viscous than the liquid from which it is formed.

[0075] When an indefinite or definite article is used when referring to a singular noun (eg, "a", "an" or "the"), this includes a plural of that noun unless something else is specifically stated.

[0076] When the term "comprising" is used in the present description and claims, other elements are not excluded. For the purposes of the present invention, the term "consisting of" is considered a preferred embodiment of the term "comprising". If hereinafter a group is defined as comprising at least a certain amount of embodiments, this is also considered to disclose a group that preferably consists of only these embodiments.

[0077] Terms like "obtainable" or "definable" and "obtained" or "definable" can be used interchangeably. This means, for example, that unless the context clearly dictates otherwise, the term "obtained" is not intended to indicate, for example, that an embodiment must be obtained by, for example, a series of steps following the term "obtained", although such a limited understanding is always included as a preferred embodiment by the term "obtained" or "definable".

[0078] Whenever the terms "including" or "having" are used, these terms are intended to be equivalent to "comprising" as defined above. DETAILED DESCRIPTION OF THE INVENTION

[0080] The method of the present invention for producing a white UV-absorbing surface-reacted calcium carbonate doped with a titanium species comprises the following steps: a) providing a material comprising calcium carbonate, b) providing at least one H3O + ion donor, c) providing at least one substance comprising titanium, and d) reacting the at least one H3O + The calcium carbonate-containing material of step a) is treated with an ion donor to form an aqueous suspension of surface-reacted calcium carbonate, and wherein the at least one titanium-containing substance of step c) is added before and / or during and / or after step d).

[0081] The following preferred embodiments of the white UV-absorbing titanium-doped surface-reacted calcium carbonate of the present invention will be described in more detail. It should be understood that these embodiments and details also apply to the products of the present invention and their use as well as the method of the present invention for preparing the white UV-absorbing titanium-doped surface-reacted calcium carbonate.

[0082] Method step a)

[0083] According to step a) of the method of the invention, a material comprising calcium carbonate is provided.

[0084] According to one embodiment, the at least one calcium carbonate-containing material has a calcium carbonate content of at least 80 wt.-%, preferably 85 wt.-%, more preferably 90 wt.-% and most preferably 95 wt.-%, based on the total weight of the calcium carbonate-containing material. According to another embodiment, the at least one calcium carbonate-containing material consists of calcium carbonate.

[0085] The material comprising calcium carbonate may be selected from natural ground calcium carbonate, precipitated calcium carbonate or mixtures thereof. The natural ground calcium carbonate may preferably be selected from marble, limestone and / or chalk, and / or the precipitated calcium carbonate may preferably be selected from vaterite, calcite and / or aragonite.

[0086] According to one embodiment of the present invention, the material comprising calcium carbonate is natural ground calcium carbonate and / or precipitated calcium carbonate, preferably natural ground calcium carbonate is selected from marble, chalk, limestone and mixtures thereof, and / or the precipitated calcium carbonate is selected from precipitated calcium carbonate having aragonite, vaterite or calcite crystal form and mixtures thereof.

[0087] "Natural ground calcium carbonate" (GCC) is understood to be made from naturally occurring forms of calcium carbonate, mined from sedimentary rocks such as limestone or chalk, or from metamorphic marble rocks, eggshells or shells. Calcium carbonate is known to exist as three types of crystal polymorphs: calcite, aragonite and vaterite. Calcite, the most common crystal polymorph, is considered to be the most stable crystalline form of calcium carbonate. Less common is aragonite, which has a discrete or clustered needle-shaped orthorhombic crystal structure. Vaterite is the rarest calcium carbonate polymorph and is generally unstable. Ground calcium carbonate is almost entirely a calcite polymorph, which is said to be a trigonal-rhombohedral system and represents the most stable form of calcium carbonate polymorphs. In the meaning of the present application, the term "source" of calcium carbonate refers to the naturally occurring mineral material from which calcium carbonate is obtained. The source of calcium carbonate may contain additional naturally occurring components, such as magnesium carbonate, aluminosilicates, etc.

[0088] In general, the grinding of natural ground calcium carbonate can be a dry grinding or wet grinding step, and can be carried out with any conventional grinding device, for example, under conditions such that the pulverization is mainly caused by the impact with the second body, i.e., in one or more of the following: ball mill, rod mill, vibrating mill, roller crusher, centrifugal impact mill, vertical bead mill, grinding mill, pin crusher, hammer mill, crusher, shredder, disperser (de-clumper), scraper cutter or other such equipment known to the technician. If the mineral material containing calcium carbonate comprises a wet-ground mineral material containing calcium carbonate, the grinding step can be carried out under conditions such that autogenous grinding occurs and / or by horizontal ball milling and / or other such methods known to the technician. The mineral material containing ground calcium carbonate thus obtained by wet processing can be rinsed and dehydrated by known methods, for example, by flocculation, filtration or forced evaporation before drying. The subsequent drying step (if necessary) can be carried out in a single step such as spray drying, or in at least two steps. It is also common that such mineral materials undergo a beneficiation step (such as flotation, bleaching or magnetic separation step) to remove impurities.

[0089] According to one embodiment of the present invention, the source of natural ground calcium carbonate (GCC) is selected from marble, chalk, limestone or mixtures thereof. Preferably, the source of ground calcium carbonate is marble, and more preferably magnetic marble. According to one embodiment of the present invention, GCC is obtained by dry grinding. According to another embodiment of the present invention, GCC is obtained by wet grinding and subsequent drying.

[0090] According to one embodiment of the invention, the calcium carbonate comprises one type of natural ground calcium carbonate.According to another embodiment of the invention, the calcium carbonate comprises a mixture of two or more types of natural ground calcium carbonate selected from different sources.

[0091] "Precipitated calcium carbonate" (PCC) in the meaning of the present invention is a synthetic material, usually by precipitation after the reaction of carbon dioxide and calcium hydroxide in an aqueous environment or by precipitating calcium ions and carbonates such as CaCl and NaCO from a solution to obtain. Another possible way to produce PCC is the lime soda process, or the Solvay process in which PCC is a byproduct of ammonia production. Precipitated calcium carbonate exists in three main crystal forms: calcite, aragonite and vaterite, and there are many different polymorphs (crystal habits) in each of these crystal forms. Calcite has a trigonal structure, wherein typical crystal habits are such as scalenohedron (S-PCC), rhombohedron (R-PCC), hexagonal prism, oblique hexahedron, colloid (C-PCC), cube and prism (P-PCC). Aragonite is an orthorhombic structure, with double hexagonal prism crystals, and various thin elongated prisms, curved leaves, steep cones, chisel-shaped crystals, branched trees and typical crystal habits of coral or worm-like forms. Vaterite belongs to the hexagonal crystal system. The obtained PCC slurry may be mechanically dewatered and dried.

[0092] According to one embodiment of the present invention, the calcium carbonate is precipitated calcium carbonate, preferably comprising aragonite, vaterite or calcite mineralogical crystal forms or mixtures thereof.

[0093] Precipitated calcium carbonate can be prepared by using at least one H3O + The ion donor treatment is preceded by grinding in the same manner as described above for grinding natural ground calcium carbonate.

[0094] According to one embodiment of the present invention, the calcium carbonate containing material is in the form of particles having a weight median particle size d 50 (by weight) is 0.05-10 μm, preferably 0.2-5.0 μm, more preferably 0.4-3.0 μm and most preferably 0.6-1.2 μm, especially 0.7 μm. According to a further embodiment of the present invention, the calcium carbonate-containing material is in the form of particles having a top cut particle size d 98 (by weight) is from 0.15 to 55 μm, preferably from 1 to 40 μm, more preferably from 2 to 25 μm and most preferably from 3 to 15 μm, especially 4 μm.

[0095] The material containing calcium carbonate may have a mass of 1-200 m 2 The specific surface area (BET) of the calcium carbonate-containing material is 1-150 m / g, as measured using nitrogen and the BET method according to ISO 9277:2010. According to one embodiment, the specific surface area (BET) of the calcium carbonate-containing material is 1-150 m / g. 2 / g, preferably 2-60m 2 / g, and more preferably 2-15m 2 / g, as measured using nitrogen and the BET method according to ISO 9277:2010.

[0096] The calcium carbonate containing material can be used dry or in the form of an aqueous suspension. According to a preferred embodiment, the calcium carbonate containing material is in the form of an aqueous suspension having a solids content in the range of 1 wt % to 90 wt %, preferably 3 wt % to 60 wt %, more preferably 5 wt % to 40 wt % and most preferably 10 wt % to 25 wt %, based on the weight of the aqueous suspension.

[0097] The term "aqueous" suspension refers to a system in which the liquid phase comprises water, preferably consists of water. However, the term does not exclude that the liquid phase of the aqueous suspension comprises a small amount of at least one water-miscible organic solvent selected from methanol, ethanol, acetone, acetonitrile, tetrahydrofuran and mixtures thereof. If the aqueous suspension comprises at least one water-miscible organic solvent, the liquid phase of the aqueous suspension comprises an amount of 0.1-40.0 wt.-%, preferably 0.25-30.0 wt.-%, more preferably 0.5-20.0 wt.-% and most preferably 1.0-10.0 wt.-% of at least one water-miscible organic solvent, based on the total weight of the liquid phase of the aqueous suspension. For example, the liquid phase of the aqueous suspension consists of water.

[0098] According to a preferred embodiment of the present invention, the aqueous suspension consists of water and a material comprising calcium carbonate.

[0099] Alternatively, the aqueous suspension of the material comprising calcium carbonate may include additional additives such as dispersants. Suitable dispersants may be selected from polyphosphates, and particularly tripolyphosphates. Another suitable dispersant may be selected from homopolymers or copolymers or mixtures thereof based on polycarboxylates such as acrylic acid, methacrylic acid, maleic acid, fumaric acid or itaconic acid and acrylamide. The homopolymers or copolymers of polycarboxylates may be completely or partially neutralized, such as at least 70%, or at least 80% or at least 90% of the acid groups are neutralized. Neutralization means that the proton of the carboxylic acid is exchanged with another cation such as sodium and / or calcium cations. According to a preferred embodiment, the homopolymers or copolymers of polycarboxylates are completely neutralized and most preferably completely neutralized by sodium and / or calcium ions. Acrylic homopolymers or copolymers are particularly preferred. Most preferably, acrylic homopolymers or copolymers completely neutralized by sodium and / or calcium ions. The weight average molecular weight M of such a product is preferably 100-1500 wt %; w Preferably in the range of 2000-15000 g / mol, wherein the weight average molecular weight M w 3000-7000 g / mol or 3500-6000 g / mol is particularly preferred. According to an exemplary embodiment, the dispersant is a dispersant having a weight average molecular weight M wIt is 2000-15000 g / mol, preferably 3000-7000 g / mol and most preferably 3500-6000 g / mol of sodium polyacrylate.

[0100] According to one embodiment of the present invention, the calcium carbonate-containing material provided in process step a) is natural ground calcium carbonate and / or precipitated calcium carbonate, preferably an aqueous suspension of natural ground calcium carbonate and / or precipitated calcium carbonate having a solids content in the range of 1 wt.-% to 90 wt.-%, preferably 3 wt.-% to 60 wt.-%, more preferably 5 wt.-% to 40 wt.-% and most preferably 10 wt.-% to 25 wt.-%, based on the weight of the aqueous suspension.

[0101] Method step b)

[0102] According to step b) of the method of the present invention, at least one H3O + In the context of the present invention, "H3O + The "ion donor" is a Bronsted acid and / or acid salt, i.e. a salt containing an acidic hydrogen.

[0103] At least one H3O + The ion donor can be any moderately strong or weak acid, or a mixture thereof, which produces H3O under the preparation conditions. + According to the present invention, at least one H3O + The ion donor can also be an acid salt, thereby generating H3O under the preparation conditions. + According to the present invention, at least one H3O + The ion donor does not have a pK a A strong acid of less than 0. Such strong acids are known to the skilled person as, for example, sulfuric acid or hydrochloric acid.

[0104] According to one embodiment, at least one H3O + The ion donor has a pK at 20°C. a A medium-strong acid with a pK value of 0-2.5. a is 0-2.5, then H3O + The ion donor is preferably H3PO4. At least one H3O + The ion donor can also be an acid salt, such as H2PO4 - (through the corresponding cations such as Li + 、Na + or K + at least partially neutralized) or HPO4 2- (through the corresponding cations such as Li + 、Na + , K + Mg 2+ or Ca 2+at least partially neutralized). at least one H3O + The ion donor may also be a mixture of one or more acids and one or more acid salts.

[0105] According to another embodiment, at least one H3O + The ion donor is a weak acid having a pK greater than 2.5 and less than or equal to 7 with respect to the ionization of the first available hydrogen when measured at 20°C. a Subsequently, at least one water-soluble salt is additionally provided, which in the case of a hydrogen-containing salt has a pK value greater than 7 when measured at 20° C. related to the ionization of the first available hydrogen. a , and a salt anion capable of forming a water-insoluble calcium salt. According to a preferred embodiment, the weak acid has a pK from greater than 2.5 to 5 at 20°C. a The water-soluble salt may be added dropwise or in one step. In the case of dropwise addition, the addition preferably occurs within a period of 10 minutes. More preferably, the salt is added in one step.

[0106] According to one embodiment of the present invention, at least one H3O + The ion donor is selected from phosphoric acid, citric acid, acid salts and mixtures thereof. Preferably at least one H3O + The ion donor is selected from phosphoric acid, H2PO4 - (Selected from Li + 、Na + and / or K + The cations are at least partially neutralized), HPO4 2- (Selected from Li + 、Na + , K + Mg 2+ and / or Ca 2+ cations at least partially neutralized), citric acid, and mixtures thereof, more preferably at least one H3O + The ion donor is selected from phosphoric acid, citric acid or a mixture thereof, and most preferably at least one H3O + The ion donor is phosphoric acid.

[0107] At least one H3O may be provided in solid form or in the form of a solution + According to a preferred embodiment, at least one H3O + ion donor.

[0108] According to one embodiment, at least one H3O is contained in an amount of 0.1-100 wt %, preferably in an amount of 1-80 wt %, more preferably in an amount of 10-50 wt %, and most preferably in an amount of 20-40 wt %. + The ion donor is provided in the form of an aqueous solution of at least one H3O + The ion donor is based on the total weight of the aqueous solution.

[0109] According to one embodiment, at least one H3O + The molar ratio of ion donor to calcium carbonate containing material is 0.01-4, preferably 0.02-2, more preferably 0.05-1 and most preferably 0.1-0.58.

[0110] According to another embodiment, at least one H3O is provided in an amount of 1-40 wt%, preferably 5-30 wt%, more preferably 10-20 wt%, and most preferably 15-18 wt%. + Ion donor, based on the total weight of the material comprising calcium carbonate.

[0111] As an alternative, H3O can also be added to the water before adding the material containing calcium carbonate. + ion donor.

[0112] Method step c)

[0113] According to step c) of the method of the invention, at least one substance comprising titanium is provided.

[0114] According to one embodiment of the present invention, the at least one substance containing titanium is selected from titanium salts, titanium hydroxide, titanium dioxide, and mixtures thereof.

[0115] According to a preferred embodiment of the present invention, the substance containing titanium is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the substance containing titanium is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof.

[0116] A "titanium salt" within the meaning of the present invention is a chemical compound consisting of an ionic combination of cations (positively charged ions) and anions (negatively charged ions) comprising titanium such that the product is electrically neutral (has no net charge).

[0117] The anion may be an inorganic anion such as chloride ion (Cl - ), bromide ion (Br -), fluoride ion (F - ), iodide ion (I - ), sulfate (SO 2- 4) or nitrate (NO3 - ), or organic anions such as acetate (CH3CO - 2).

[0118] The cation may be a titanium cation such as Ti 2+ 、Ti 3+ or Ti 4+ cation.

[0119] Examples of suitable titanium salts are titanium bromides such as TiBr4 or TiBr3, titanium fluorides such as TiF4 or TiF3, titanium iodide (TiI4), titanium chloride (TiCl4), titanium oxysulfate (TiOSO4) also known as titanium oxysulafonate, titanium sulfate (Ti2(SO4)3), titanium nitrate (Ti(NO3)4) or titanium acetate (Ti(C2H3O2)4). The titanium salt may be an amorphous salt or a hydrate salt.

[0120] As used herein, "hydrate" is an inorganic salt containing water molecules in a certain ratio as an integral part of the crystal. Depending on the number of water molecules per formula unit of the salt, the hydrate can be designated as a monohydrate, dihydrate, trihydrate, tetrahydrate, pentahydrate, hexahydrate, heptahydrate, octahydrate, nonahydrate, decahydrate, hemihydrate, etc.

[0121] "Titanium hydroxide" within the meaning of the present invention is a compound comprising a compound having the formula OH - A chemical compound containing a diatomic anion of a metal. The hydroxide ion consists of oxygen and hydrogen atoms held together by a single covalent bond and carries a negative charge. Examples of suitable titanium hydroxides are Ti(OH)4 or Ti(OH)3.

[0122] "Titanium dioxide" within the meaning of the present invention is a chemical compound comprising titanium and oxygen, wherein the oxygen has an oxidation number (II). Examples of suitable titanium dioxides are TiO2, TiO, Ti2O3, Ti3O or Ti2O, delta-TiO x Where x = 0.68–0.75 or Ti n O 2n-1 Wherein n ranges from 3 to 9 (inclusive).

[0123] According to a preferred embodiment, the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof and most preferably the titanium-containing substance is titanyl sulfate.

[0124] The substance containing titanium may be a water-soluble or water-insoluble substance.

[0125] According to one embodiment, at least one substance comprising titanium is provided in an amount of 0.1-20 wt. % titanium element, preferably 0.5-15 wt. %, more preferably 1.0-10 wt. % and most preferably 2.5-7.5 wt. %, based on the total weight of the material comprising calcium carbonate. The term "titanium element" in the meaning of the present invention refers to the weight of titanium in the substance comprising titanium, assuming that titanium is present as Ti 0 Existence is also referred to as elemental titanium in substances containing titanium.

[0126] According to another embodiment, the at least one titanium containing substance is provided in an amount of 0.1-20 mol% titanium, preferably 0.5-15 mol%, more preferably 1.0-10 mol%, and most preferably 2.5-7.5 mol%, based on the total amount of the calcium carbonate containing material.

[0127] The at least one substance comprising titanium may be provided in the form of a solution, a suspension or as a dry material.

[0128] According to one embodiment, at least one substance comprising titanium is provided as a dry material. The dry material may be in the form of a powder, flakes, pellets, etc., and is most preferably in the form of a powder.

[0129] According to another embodiment, the at least one substance comprising titanium is provided in the form of a solution or a suspension. Preferably, the solution or suspension comprises the at least one substance comprising titanium in an amount of 0.01-10 wt. %, preferably in an amount of 0.1-8 wt. %, more preferably in an amount of 0.4-5 wt. %, and most preferably in an amount of 0.8-2 wt. %, based on the total weight of the solution or suspension.

[0130] The solution or suspension may be an aqueous solution or suspension, or an organic solution or suspension. Alternatively, the solution or suspension may comprise both water and an organic solvent, which is miscible with water in any ratio, preferably in a water:solvent ratio of 100:0.1-100:200, preferably 100:1-100:150, more preferably 100:5-100:120 and most preferably 100:10-100:100, based on the weight of water and the dry weight of the solvent. Possible organic solvents of the present invention are, for example, methanol, ethanol, ethylene glycol, glycerol, acetone or propanol.

[0131] According to a preferred embodiment, the solution or suspension is an aqueous solution or suspension comprising water and a substance comprising titanium, preferably consisting of water and a substance comprising titanium.

[0132] Method step d)

[0133] According to step d) of the process of the invention, the calcium carbonate-containing material of step a) is reacted in an aqueous medium with at least one H3O + The invention relates to an ion donor treatment to form a suspension of surface-reacted calcium carbonate, and wherein the at least one titanium-containing substance of step c) is added before and / or during and / or after step d).

[0134] The method can be performed by providing an aqueous suspension of a material comprising calcium carbonate and adding at least one H3O + The ion donor is thus at least one H3O + Ion donor treatment of materials containing calcium carbonate. At least one H3O may be added to the suspension as a concentrated solution or a more dilute solution. + As an alternative, it is also possible to add at least one H3O + The ion donor solution is added to a material containing calcium carbonate to form a solution containing at least one H3O + The ion donor treats the material comprising calcium carbonate.

[0135] Medium to strong acid can be used for H3O + Ion donor treatment. It is also possible to use a Medium to strong acid in the range of 0 to 2.5 H3O + Ion donor treatment.

[0136] In a preferred embodiment, H3O is repeated at least once, more preferably several times. + Ion donor treatment step. According to one embodiment, at least one H3O is added for a period of at least about 5 minutes, preferably at least about 10 minutes, typically about 10 to about 20 minutes, more preferably about 30 minutes, even more preferably about 45 minutes, and sometimes about 1 hour or longer. + ion donor.

[0137] H3O + After the ion donor treatment, the pH of the aqueous suspension measured at 20°C naturally reaches a value of greater than 6.0, preferably greater than 6.5, more preferably greater than 7.0, even more preferably greater than 7.5, thereby preparing the surface-reacted natural or precipitated calcium carbonate as an aqueous suspension having a pH of greater than 6.0, preferably greater than 6.5, more preferably greater than 7.0, even more preferably greater than 7.5.

[0138] In a particularly preferred embodiment, the surface-reacted calcium carbonate is the reaction product of natural ground calcium carbonate (GNCC) and phosphoric acid.

[0139] Further details on the preparation of surface-reacted natural calcium carbonate are disclosed in WO0039222A1, WO2004083316A1, WO2005121257A2, WO2009074492A1, EP2264108 A1, EP2264109 A1 and US20040020410 A1, the contents of these references are hereby included in the present application.

[0140] Similarly, a surface-reacted precipitated calcium carbonate is obtained. As can be seen in detail from WO2009074492 A1, by reacting the precipitated calcium carbonate with H3O in an aqueous medium, + ions and anions dissolved in an aqueous medium and capable of forming a water-insoluble calcium salt to form a slurry of surface-reacted precipitated calcium carbonate to obtain a surface-reacted precipitated calcium carbonate, wherein the surface-reacted precipitated calcium carbonate comprises an insoluble, at least partially crystalline calcium salt of the anion formed on the surface of at least a portion of the precipitated calcium carbonate.

[0141] The dissolved calcium ions correspond to the calcium carbonate precipitated by H3O + The H3O is a solution of calcium ions in excess of naturally occurring dissolved calcium ions, wherein the H3O is provided only in the form of counterions to the anions, i.e., via addition of anions in acid or non-calcium salt form and in the absence of any additional calcium ions or sources of calcium ion generation. + ion.

[0142] The excess dissolved calcium ions are preferably provided by the addition of a soluble neutral or acid calcium salt, or by the addition of an acid or a neutral or acid non-calcium salt which generates a soluble neutral or acid calcium salt in situ.

[0143] The H3O may be provided by adding an acid or an acid salt of the anion, or both to provide all or part of the excess dissolved calcium ions. + ion.

[0144] The at least one substance comprising titanium of step c) is added before and / or during and / or after step d). According to a preferred embodiment of the present invention, the at least one substance comprising titanium of step c) is added before and / or during step d), and most preferably, the at least one substance comprising titanium of step c) is added during step d).

[0145] If the at least one titanium-containing substance of step c) is added after step d), the at least one H3O +The ion donor is still present in solution. If the at least one titanium-containing substance of step c) is added before step d), when the H3O of step b) is added + The at least one titanium-containing substance of step c) is still present in solution when the at least one H3O + The ion donor and at least one titanium-containing substance are present simultaneously in a composition comprising: a material comprising calcium carbonate and / or surface-reacted calcium carbonate. Without wishing to be bound by theory, the inventors believe that at least one H3O + The simultaneous presence of the ion donor and the at least one titanium-containing substance results in doping the surface-reacted calcium carbonate with the titanium substance. Thus, this method differs from the method described above in the absence of at least one H3O + In the case of an ion donor, mixing the already formed surface-reacted calcium carbonate with at least one substance comprising titanium results in only mixing (even in aqueous suspension) and will not result in doped material.

[0146] According to a preferred embodiment, there is provided a process for producing white UV absorbing surface reacted calcium carbonate doped with titanium species comprising the steps of:

[0147] a) providing a material comprising calcium carbonate,

[0148] b) Provide at least one H3O + ion donor,

[0149] c) providing at least one substance comprising titanium, and

[0150] d) treating in an aqueous medium with at least one H3O + treating the calcium carbonate-containing material of step a) with an ion donor to form an aqueous suspension of surface-reacted calcium carbonate, and

[0151] The at least one titanium-containing substance of step c) is added before and / or during step d).

[0152] According to one embodiment of the present invention, in a first step, at least one H3O of step b) is added to the calcium carbonate-containing material of step a). + The ion donor and thereafter the titanium-containing substance of step c) is added.

[0153] According to another embodiment of the present invention, in a first step, the material comprising calcium carbonate of step a) is added with the substance comprising titanium of step c) and thereafter with the at least one H3O of step b). + ion donor.

[0154] According to another embodiment of the present invention, at least one H3O +The titanium-containing substance of step c) is added together with the ion donor to the calcium carbonate-containing material of step a).

[0155] According to one embodiment of the present invention, at least one H3O of step b) is added in solid form or in the form of a solution. + The at least one H3O2 of step b) is preferably added in the form of a solution. + The ion donor and / or the at least one titanium-containing substance of step c) are preferably added in the form of a solution of at least one H3O + an ion donor and at least one substance comprising titanium of step c).

[0156] The at least one H3O of step b) may be provided in the form of a separate solution and / or in the form of a combined solution. + According to one embodiment, in step d), the material comprising calcium carbonate is treated with at least one H3O + Solution treatment of the ion donor and at least one titanium-containing substance of step c).

[0157] According to another embodiment, in step d), the material comprising calcium carbonate is treated with at least one H3O + The first solution of the first portion of the ion donor is treated and then treated with at least one H3O + The remaining portion of the ion donor and the second solution of at least one substance containing titanium of step c) are treated. The first solution may contain less than or equal to 50% by weight of at least one H3O + The ion donor is preferably less than or equal to 40 wt %, more preferably less than or equal to 30 wt %, and most preferably less than or equal to 20 wt %, based on at least one H3O + For example, the first solution may contain 0.1-50 wt % of at least one H3O + Ion donor, preferably 1-40 wt %, more preferably 5-30 wt %, and most preferably 10-20 wt %, based on at least one H3O + Total amount of ion donor.

[0158] According to yet another embodiment, in step b) a first H3O is provided + Ion donor and second H3O + ion donor, and in step d) the material comprising calcium carbonate is treated with a first + The first solution is treated with an ion donor and then with a second solution containing H3O +The ion donor and the second solution treatment of step c) at least one substance comprising titanium.

[0159] According to one embodiment, in step d), the material comprising calcium carbonate is treated with at least one H3O + The first solution of the first portion of the ion donor is treated and then treated with at least one H3O + The remaining portion of the ion donor is treated with a second solution of at least one substance comprising titanium from step c), wherein the first solution comprises less than 50% by weight of at least one H3O + Ion donor, preferably less than 40 wt %, more preferably less than 30 wt %, and most preferably less than 20 wt %, based on at least one H3O + Total amount of ion donor.

[0160] According to a preferred embodiment, in step d), the material comprising calcium carbonate comprises at least one H3O in an amount of 1-80 wt. %, preferably in an amount of 2-50 wt. %, more preferably in an amount of 5-35 wt. % and most preferably in an amount of 10-30 wt. %. + The solution treatment of the ion donor is based on the total weight of the aqueous solution.

[0161] Alternatively, according to another preferred embodiment, in step d), the material comprising calcium carbonate is treated with a solution comprising at least one substance comprising titanium in an amount of 0.01-10 wt.-% titanium element, preferably in an amount of 0.1-8 wt.-%, more preferably in an amount of 0.4-5 wt.-% and most preferably in an amount of 0.8-2 wt.-%, based on the total weight of the aqueous solution.

[0162] According to a preferred embodiment, in step d) the material comprising calcium carbonate is treated with a solution comprising: at least one H3O in an amount of 1-80 wt. %, preferably in an amount of 2-50 wt. %, more preferably in an amount of 5-35 wt. % and most preferably in an amount of 10-30 wt. % + ion donor, based on the total weight of the aqueous solution, and at least one substance containing titanium in an amount of 0.01-10 wt %, preferably in an amount of 0.1-8 wt %, more preferably in an amount of 0.4-5 wt % and most preferably in an amount of 0.8-2 wt %, based on the total weight of the aqueous solution.

[0163] According to a preferred embodiment, the calcium carbonate-containing material is natural ground calcium carbonate, at least one H3O +The ion donor is phosphoric acid and / or citric acid, and at least one titanium-containing substance is selected from titanium salts, titanium hydroxide, titanium oxide and mixtures thereof, preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof.

[0164] According to another preferred embodiment, the calcium carbonate-containing material is natural ground calcium carbonate, at least one H3O + The ion donor is phosphoric acid, and at least one titanium-containing substance is selected from titanium salts, titanium hydroxide, titanium oxide and mixtures thereof, preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof, even more preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof, and most preferably the titanium-containing substance is titanyl sulfate.

[0165] According to a preferred embodiment, the calcium carbonate-containing material is natural ground calcium carbonate, at least one H3O + The ion donor is phosphoric acid and / or citric acid, and at least one titanium-containing substance is selected from titanium salts, titanium hydroxide, titanium oxide and mixtures thereof, preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanium oxysulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanium oxysulfate and mixtures thereof and H3O is added before the at least one titanium-containing substance + ion donor.

[0166] According to a preferred embodiment, the calcium carbonate-containing material is natural ground calcium carbonate, at least one H3O + The ion donor is phosphoric acid and / or citric acid, and at least one titanium-containing substance is selected from titanium salts, titanium hydroxide, titanium oxide and mixtures thereof, preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanium oxysulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanium oxysulfate and mixtures thereof and H3O is added to the solution before adding it to the material comprising calcium carbonate. + An ion donor is mixed with at least one substance containing titanium in the solution.

[0167] According to one embodiment of the present invention, in step d), the pH value of the obtained aqueous suspension of surface-reacted calcium carbonate is 4.5-11, preferably 5.5-10 and most preferably 6.0-8.0.

[0168] According to one embodiment of the present invention, step d) is carried out at a temperature of 20-95°C, preferably 30-85°C, more preferably 40-80°C, even more preferably 50-75°C and most preferably 65-73°C.

[0169] According to one embodiment, method step d) is performed for at least 1 minute, preferably for at least 5 minutes, more preferably for at least 10 minutes and most preferably for at least 15 minutes. According to one embodiment, at least one H3O is added for a period of at least 1 minute, preferably at least 5 minutes, and more preferably at least 10 minutes. + ion donor, and thereafter at least one substance comprising titanium is added for the same period of time.

[0170] This can be accomplished by simply adding, for example, at least one H3O + The ion donor and / or at least one substance comprising titanium is poured, discharged or injected into the material comprising calcium carbonate to carry out method step d). According to one embodiment, method step d) is carried out under mixing conditions. Suitable mixing methods are known to the technician. Examples of suitable mixing methods are shaking, mixing, stirring, agitation, ultrasound or inducing turbulence or laminar flow by means of, for example, baffles or thin sheets. Suitable mixing equipment is known to the technician and can be selected, for example, from agitators such as rotor-stator systems, blade stirrers, propeller stirrers, turbine stirrers or anchor stirrers, static mixers such as pipelines comprising baffles or thin sheets. According to an exemplary embodiment of the present invention, a rotor-stator stirrer system is used.

[0171] According to another exemplary embodiment, the suspension formed is mixed in step d) so as to form a substantially laminar flow. The skilled person will adjust the mixing conditions such as mixing speed and temperature according to his process equipment.

[0172] Depending on the amount of water introduced during step d) by contacting the above-mentioned compounds, additional water may be introduced, for example, during process step d) in order to control and / or maintain and / or achieve a desired solid content or Brookfield viscosity of the aqueous suspension obtained. According to one embodiment, the solid content of the mixture obtained in step d) is 5-80% by weight, preferably 20-78% by weight, based on the total weight of the mixture. The Brookfield viscosity of the aqueous suspension obtained may be 10-10000 mPa·s, preferably 50-1000 mPa·s.

[0173] The process of the present invention can be carried out as a continuous process or as a batch process, preferably as a batch process.

[0174] In another embodiment of the preparation of the surface-reacted natural or precipitated calcium carbonate, the natural or precipitated calcium carbonate is reacted with one or more H3O +The ion donor is reacted in the presence of at least one compound selected from silicates, aluminum hydroxide, alkaline earth metal aluminates such as sodium aluminate or potassium aluminate, magnesium oxide, or mixtures thereof. Preferably, at least one silicate is selected from aluminum silicate, calcium silicate, or alkaline earth metal silicate. One or more H3O + The ion donors are previously added to the aqueous suspension containing natural or precipitated calcium carbonate.

[0175] Alternatively, natural or precipitated calcium carbonate is reacted with one or more H3O + The reaction of the ion donor may be carried out by adding a silicate and / or aluminum hydroxide and / or alkaline earth aluminate and / or magnesium oxide component to an aqueous suspension of natural or precipitated calcium carbonate. Further details on the preparation of surface-reacted natural or precipitated calcium carbonate in the presence of at least one silicate and / or aluminum hydroxide and / or alkaline earth aluminate component are disclosed in WO2004083316 A1, the content of which is hereby included in the present application.

[0176] Additional method steps

[0177] According to one embodiment, the method of the invention further comprises the step of agitating the aqueous suspension after step d). Preferably, the suspension is agitated for at least 1 minute, preferably for at least 5 minutes, more preferably for at least 10 minutes and most preferably for at least 15 minutes.

[0178] According to another embodiment, the white UV-absorbing, titanium-doped, surface-reacted calcium carbonate can be kept in suspension and can be optionally further stabilized by a dispersant. Conventional dispersants known to the skilled person can be used. Preferred dispersants contain polyacrylic acid and / or carboxymethyl cellulose. However, other dispersants are also possible. The skilled person will choose the dispersant according to his equipment and the intended use of the white UV-absorbing, titanium-doped, surface-reacted calcium carbonate. According to a preferred embodiment, the white UV-absorbing, titanium-doped, surface-reacted calcium carbonate is separated from the aqueous suspension, for example by filtration, and thereafter a dispersant is added to the filter cake, preferably in the form of a solution or dispersion. The skilled person knows how to filter and redisperse the white UV-absorbing, titanium-doped, surface-reacted calcium carbonate and will choose the dispersant and separation method according to his equipment and intended use.

[0179] The aqueous suspension obtained after step d) can be further processed, for example the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species can be separated from the aqueous suspension and / or subjected to a drying step.

[0180] According to one embodiment, the method of the present invention further comprises a step e) of separating the white UV absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step d). Thus, the method for producing white UV absorbing surface-reacted calcium carbonate doped with titanium species may comprise the following steps:

[0181] a) providing a material comprising calcium carbonate,

[0182] b) Provide at least one H3O + ion donor,

[0183] c) providing at least one substance comprising titanium, and

[0184] d) treating in an aqueous medium with at least one H3O + treating the calcium carbonate-containing material of step a) with an ion donor to form an aqueous suspension of surface-reacted calcium carbonate, and

[0185] wherein the at least one substance comprising titanium of step c) is added before and / or during and / or after step d), and

[0186] e) separating the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained from step d).

[0187] The white UV-absorbing titanium-doped surface-reacted calcium carbonate obtained from step d) can be separated from the aqueous suspension by any conventional separation means known to the skilled person. According to one embodiment of the present invention, the white UV-absorbing titanium-doped surface-reacted calcium carbonate is mechanically and / or thermally separated in method step e). Examples of mechanical separation methods are filtration (e.g., by drum filters or filter presses), nanofiltration or centrifugation. Examples of thermal separation methods are concentration methods by applying heat, for example, in an evaporator. According to a preferred embodiment, the surface-reacted calcium carbonate is separated in method step e) by solvent evaporation and / or filter press.

[0188] After separation, the white UV-absorbing titanium-doped surface-reacted calcium carbonate can be dried in order to obtain dry white UV-absorbing titanium-doped surface-reacted calcium carbonate. According to one embodiment, the method of the present invention further comprises a step f): drying the white UV-absorbing titanium-doped surface-reacted calcium carbonate after step d) or after step e) (if present) at a temperature in the range of 60-600° C., preferably 80-450° C., most preferably 95-400° C., preferably until the moisture content of the white UV-absorbing titanium-doped surface-reacted calcium carbonate is less than 1% by weight, based on the total weight of the dry white UV-absorbing titanium-doped surface-reacted calcium carbonate.

[0189] According to one embodiment, the method of the present invention further comprises a step f) of drying the white UV absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step d) and / or step e). Thus, the method for producing a white UV absorbing surface-reacted calcium carbonate doped with titanium species may comprise the following steps:

[0190] a) providing a material comprising calcium carbonate,

[0191] b) Provide at least one H3O + ion donor,

[0192] c) providing at least one substance comprising titanium, and

[0193] d) treating in an aqueous medium with at least one H3O + treating the calcium carbonate-containing material of step a) with an ion donor to form an aqueous suspension of surface-reacted calcium carbonate, and

[0194] wherein the at least one substance comprising titanium of step c) is added before and / or during and / or after step d), and

[0195] e) separating the white UV-absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained from step d) and

[0196] f) drying the surface-reacted calcium carbonate.

[0197] In general, the drying step f) can occur using any suitable drying equipment and can, for example, include thermal drying and / or drying under reduced pressure using equipment such as evaporators, flash dryers, ovens, spray dryers and / or drying in a vacuum chamber. The drying step f) can be carried out under reduced pressure, ambient pressure or under increased pressure. For temperatures below 100° C., it may be preferred to carry out the drying step under reduced pressure. The drying step can be carried out, for example, for at least 30 seconds, at least 1 minute, 2 minutes, 5 minutes, 10 minutes, 30 minutes, 1 hour, 2 hours, 12 hours or 1 day. The skilled person can select the drying time according to the equipment, water content and intended use.

[0198] According to a preferred embodiment, the separation is carried out by thermal methods. This allows the white UV-absorbing surface-reacted calcium carbonate doped with titanium species to be subsequently dried without changing the equipment.

[0199] According to one embodiment, the surface-reacted calcium carbonate is dried in process step f) until the moisture content of the white, UV-absorbing, surface-reacted calcium carbonate doped with a titanium species is less than or equal to 1.0 wt.-%, preferably less than or equal to 0.5 wt.-% and more preferably less than or equal to 0.2 wt.-%, based on the total weight of the dried, white, UV-absorbing, surface-reacted calcium carbonate doped with a titanium species.

[0200] According to another embodiment, the process of the present invention further comprises a step g) of treating the surface of the white UV absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step d) and / or step e) and / or step f). Thus, the process for producing a white UV absorbing surface-reacted calcium carbonate doped with titanium species may comprise the following steps:

[0201] a) providing a material comprising calcium carbonate,

[0202] b) Provide at least one H3O + ion donor,

[0203] c) providing at least one substance comprising titanium, and

[0204] d) treating in an aqueous medium with at least one H3O + treating the calcium carbonate-containing material of step a) with an ion donor to form an aqueous suspension of surface-reacted calcium carbonate,

[0205] wherein the at least one substance comprising titanium of step c) is added before and / or during and / or after step d), and

[0206] e) separating the white UV-absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained from step d) and

[0207] f) drying the surface-reacted calcium carbonate and

[0208] g) Treating the surface of the obtained white UV-absorbing surface-reacted calcium carbonate doped with titanium species.

[0209] In principle, the treatment step g) can occur using any suitable treatment agent, such as a hydrophobic agent such as a fatty acid. Such hydrophobic agents such as stearic acid and palmitic acid are known to the skilled person and are commercially available. Surface treatment of the white UV absorbing surface-reacted calcium carbonate doped with a titanium species can affect the rheological properties of the material.

[0210] The inventors surprisingly found that surface-reacted calcium carbonate particles doped with titanium substances can be prepared by the method of the present invention. The method for producing these particles is an easy and fast method, and the product obtained is affordable and especially easy to handle. The method can be carried out in standard equipment without causing significant burden on humans and the environment. Such methods and products are advantageous because the final consumer does not have to handle particles containing titanium dioxide in powder form, and the powder contains submicron or nanometer-sized titanium dioxide particles. Therefore, floating dust can be reduced or eliminated, which can occur when two compounds (surface-reacted calcium carbonate and titanium-containing materials (e.g., titanium dioxide)) are mixed in the form of a dry product, which can cause health problems, especially when inhaled. In addition, particle separation during transportation can be reduced or eliminated, which can occur when two compounds (surface-reacted calcium carbonate and titanium dioxide) are mixed in the form of a dry product.

[0211] White UV absorbing titanium doped surface reacted calcium carbonate

[0212] According to another aspect of the present invention, there is provided a white UV absorbing surface-reacted calcium carbonate doped with titanium species, comprising calcite and hydroxyapatite and having a specific surface area of ​​15 m 2 / g-200m 2 / g, which is measured using nitrogen and the BET method according to ISO9277:2010,

[0213] wherein the weight ratio of calcite to hydroxyapatite is 99:1 to 1:99, based on the dry weight of calcite and the dry weight of hydroxyapatite, and

[0214] The titanium material is present in an amount of 0.01-20 wt % titanium element, based on the total dry weight of the surface-reacted calcium carbonate.

[0215] A white, UV-absorbing, surface-reacted calcium carbonate doped with a titanium substance can be obtained by the method of the present invention. Therefore, a white, UV-absorbing, surface-reacted calcium carbonate doped with a titanium substance can be obtained by a method comprising the following steps:

[0216] a) providing a material comprising calcium carbonate,

[0217] b) Provide at least one H3O + ion donor,

[0218] c) providing at least one substance comprising titanium, and

[0219] d) treating in an aqueous medium with at least one H3O + treating the calcium carbonate-containing material of step a) with an ion donor to form an aqueous suspension of surface-reacted calcium carbonate, and

[0220] The at least one titanium-containing substance of step c) is added before and / or during and / or after step d).

[0221] The white UV absorbing surface-reacted calcium carbonate doped with a titanium species may be present in a suspension or slurry or may be present as a dry white UV absorbing surface-reacted calcium carbonate doped with a titanium species.

[0222] According to one embodiment, the white UV absorbing surface-reacted calcium carbonate doped with titanium species has a surface area of ​​25 m 2 / g-180m 2 / g, more preferably 30m 2 / g-160m 2 / g, even more preferably 45m 2 / g-150m 2 / g, most preferably 50m 2 / g-140m 2 The specific surface area of ​​the titanium-doped calcium carbonate may be 55 m / g, which is measured using nitrogen and the BET method according to ISO 9277:2010. For example, a white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species may have a specific surface area of ​​55 m / g. 2 / g-100m 2 / g, which is measured using nitrogen and the BET method according to ISO 9277:2010. The BET specific surface area in the meaning of the present invention is defined as the surface area of ​​the particles divided by the mass of the particles. The specific surface area as used herein is measured by adsorption using the BET isotherm (ISO 9277:2010) and is specified in m 2 The unit is / g.

[0223] Additionally or alternatively, the white UV-absorbing surface-reacted calcium carbonate doped with titanium species has a volume-determined median particle size d of 1-100 μm, preferably 2-60 μm, more preferably 3-40 μm, even more preferably 4-30 μm and most preferably 5-15 μm. 50 (volume).

[0224] Additionally or alternatively, the white UV-absorbing surface-reacted calcium carbonate doped with titanium species has a volume-determined top cut particle size d of 2-150 μm, preferably 4-100 μm, more preferably 6-80 μm, even more preferably 8-60 μm and most preferably 10-30 μm. 98 (volume).

[0225] Value d x represents such a diameter: x% of the particles have a diameter smaller than d x This means that d 98The value is the particle size at which 98% of all particles are smaller. 98 Values ​​are also specified as "top cut". d x Values ​​may be given as volume or weight percent. 50 The (weight) value is therefore the weight median particle size, ie the particle size below which 50% by weight of all particles are smaller, and d 50 The (volume) value is the volume median particle size, ie, the particle size below which 50% by volume of all particles are smaller.

[0226] The volume median particle diameter d was estimated using a Malvern Mastersizer 3000 laser diffraction system. 50 d measured using a Malvern Mastersizer 3000 laser diffraction system 50 or 98 The value indicates the diameter value such that 50% or 98% of the particles by volume, respectively, have a diameter smaller than this value. The raw data obtained by the measurement were analyzed using Mie theory, with the particle refractive index being 1.57 and the absorptivity being 0.005.

[0227] Methods and instruments are known to the skilled person and are commonly used for determining the crystallite size of fillers and pigments.

[0228] White UV absorbing titanium doped surface reacted calcium carbonate may have a range of 0.1-2.3 cm 3 / g, preferably 0.2-2.0cm 3 / g, more preferably 0.4-1.8cm 3 / g and most preferably 0.6-1.6cm 3 The intrusion specific pore volume in the particle range of / g was calculated from the results of mercury porosimetry measurements.

[0229] The particles of the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species preferably have an internal pore size in the range of 0.004-1.6 μm, more preferably in the range of 0.005 to 1.3 μm, particularly preferably 0.006-1.15 μm and most preferably 0.007 to 1.0 μm, for example 0.1 to 0.6 μm, as determined by mercury porosimetry measurements.

[0230] The specific pore volume was measured using mercury intrusion porosimetry using a Micromeritics Autopore V 9620 mercury intrusion porosimeter with a maximum applied pressure of 414 MPa (60,000 psi) of mercury equivalent to a Laplace throat of 0.004 μm (~nm). The equilibrium time used at each pressure step was 20 seconds. The sample material was sealed in a 5 cm 3The data were corrected for mercury compression, penetrometer expansion, and sample material compression using the software Pore-Comp (Gane, PAC, Kettle, JP, Matthews, GP, and Ridgway, CJ, "Void Space Structure of Compressible Polymer Spheres and Consolidated Calcium Carbonate Paper-Coating Formulations", Industrial and Engineering Chemistry Research, 35(5), 1996, pp. 1753-1764).

[0231] The total pore volume seen in the cumulative intrusion data can be divided into two regions where the intrusion data drops from 214 μm to about 1-4 μm, showing coarse packing of the sample between any strongly contributing aggregate structures. Below these diameters is fine inter-particle packing of the particles themselves. If they also have intra-particle pores, this region appears bimodal, and the intra-particle specific pore volume is defined by taking the specific pore volume of the mercury intrusion into pores finer than the modal inflection point (i.e. finer than the bimodal inflection point). The sum of these three regions yields the overall pore volume of the powder, but this is strongly dependent on the original sample compaction / sedimentation of the powder at the coarse pore end of the distribution.

[0232] By taking the first derivative of the cumulative intrusion curve, the pore size distribution based on the equivalent Laplace diameter is revealed, which inevitably includes pore shielding. The differential curve clearly shows the coarse aggregate pore structure region, the inter-particle pore region, and the intra-particle pore region (if any). Knowing the intra-particle pore size range, the remaining inter-particle and inter-aggregate pore volume can be subtracted from the total pore volume to provide the required pore volume of the individual internal pores based on the pore volume per unit mass (specific pore volume). Of course, the same subtraction principle applies to isolating any other pore size region of interest.

[0233] According to one embodiment, the white UV absorbing surface-reacted calcium carbonate doped with titanium species has

[0234] (i)25m 2 / g-180m 2 / g, more preferably 30m 2 / g-160m 2 / g, even more preferably 45m 2 / g-150m 2 / g, most preferably 50m 2 / g-140m 2Specific surface area of ​​100 g / m, measured using nitrogen and the BET method according to ISO 9277:2010, and / or

[0235] (ii) a volume-determined median particle size d of 1-100 μm, preferably 2-60 μm, more preferably 3-40 μm, even more preferably 4-30 μm and most preferably 5-15 μm 50 (volume), and / or

[0236] (iii) a volume-determined top cut particle size d of 2-150 μm, preferably 4-100 μm, more preferably 6-80 μm, even more preferably 8-60 μm and most preferably 10-30 μm 98 (volume), and / or

[0237] (iv) 0.1-2.3 cm 3 / g, preferably 0.2-2.0cm 3 / g, more preferably 0.4-1.8cm 3 / g and most preferably 0.6-1.6cm 3 The intrusion specific pore volume in the particles in the range of / g was calculated from the mercury porosimetry measurements.

[0238] According to a preferred embodiment, the white UV-absorbing surface-reacted calcium carbonate doped with titanium has a specific surface area of ​​50 m 2 / g-140m 2 / g, which is measured using nitrogen and the BET method according to ISO 9277:2010 and

[0239] (ii) a volume-determined median particle size d of 1-100 μm, preferably 2-60 μm, more preferably 3-40 μm, even more preferably 4-30 μm and most preferably 5-15 μm 50 (volume), and / or

[0240] (iii) a volume-determined top cut particle size d of 2-150 μm, preferably 4-100 μm, more preferably 6-80 μm, even more preferably 8-60 μm and most preferably 10-30 μm 98 (volume), and / or

[0241] (iv) 0.1-2.3 cm 3 / g, preferably 0.2-2.0cm 3 / g, more preferably 0.4-1.8cm 3 / g and most preferably 0.6-1.6cm 3 The intrusion specific pore volume in the particles in the range of / g was calculated from the mercury porosimetry measurements.

[0242] The white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species comprises calcite and hydroxyapatite.

[0243] "Hydroxyapatite" also referred to as hydroxyapatite (HA) in the meaning of the present invention is a naturally occurring mineral form of calcium apatite having the formula Ca5(PO4)3(OH). Hydroxyapatite may further be substituted with carbonate ions and / or halide ions such as fluoride ions, bromide ions, iodide ions, chloride ions or mixtures thereof in place of the hydroxyl groups.

[0244] "Calcite" within the meaning of the present invention is the most common crystal polymorph of calcium carbonate and is considered to be the most stable crystalline form of calcium carbonate.

[0245] According to the present invention, the weight ratio of calcite to hydroxyapatite is 99:1-1:99, based on the dry weight of calcite and the dry weight of hydroxyapatite. According to a preferred embodiment of the present invention, the weight ratio of calcite to hydroxyapatite is 80:20-20:80, more preferably 70:30-30:70 and most preferably 60:40-40:60, based on the dry weight of calcite and the dry weight of hydroxyapatite.

[0246] According to another preferred embodiment, the white UV-absorbing surface-reacted calcium carbonate doped with titanium has a specific surface area of ​​50 m 2 / g-140m 2 / g (which is measured using nitrogen and the BET method according to ISO 9277:2010) and the weight ratio of calcite to hydroxyapatite is 60:40-40:60 (based on the dry weight of calcite and the dry weight of hydroxyapatite).

[0247] In addition to calcite and hydroxyapatite, the white UV-absorbing titanium-doped surface-reacted calcium carbonate may also contain other crystal structures, such as aragonite and / or vaterite. According to a preferred embodiment of the present invention, the white UV-absorbing titanium-doped surface-reacted calcium carbonate only contains calcite and hydroxyapatite as calcium carbonate crystal structures, but no other calcium carbonate crystal structures.

[0248] The white, UV-absorbing, surface-reacted calcium carbonate is doped with a titanium substance. "Doping" with a titanium substance in the meaning of the present invention refers to the incorporation or introduction of a titanium substance into the structure of the calcium carbonate and / or hydroxyapatite. The surface-reacted calcium carbonate doped with a titanium substance may be present only in the outer layer of the surface-reacted calcium carbonate or may be present throughout the surface-reacted calcium carbonate. The doping may be present uniformly or non-uniformly in the surface-reacted calcium carbonate. According to a preferred embodiment of the present invention, the doping with a titanium substance is uniformly present throughout the surface-reacted calcium carbonate. "Doping" in the meaning of the present invention is different from a mere mixture of the surface-reacted calcium carbonate with a titanium substance or a coating with a titanium substance. The skilled person knows how to measure whether a structure is doped or merely mixed with a titanium substance, for example by SEM measurement. For example, by SEM measurement, the skilled person knows how to distinguish between single particles and attached particles.

[0249] In the meaning of the present invention, titanium material refers to titanium having an oxidation number other than zero. According to one embodiment of the present invention, titanium material in the meaning of the present invention refers to Ti 2+ 、Ti 3+ and / or Ti 4+ , preferably Ti 3+ and / or Ti 4+ , and most preferably Ti 4+ .

[0250] The titanium material is present in an amount of 0.01-20 wt% titanium element, based on the total dry weight of the surface-reacted calcium carbonate. According to a preferred embodiment of the present invention, the titanium material is present in an amount of 0.05-15 wt% titanium element, more preferably 0.1-10 wt% and most preferably 0.5-5 wt%, based on the total dry weight of the surface-reacted calcium carbonate.

[0251] According to another preferred embodiment, the white UV-absorbing surface-reacted calcium carbonate doped with titanium has a specific surface area of ​​50 m 2 / g-140m 2 / g (which is measured using nitrogen and the BET method according to ISO 9277:2010) and the titanium species is present in an amount of 0.5-5 wt% titanium element (based on the total dry weight of the surface-reacted calcium carbonate).

[0252] According to another preferred embodiment, the white UV-absorbing surface-reacted calcium carbonate doped with titanium has a specific surface area of ​​50 m 2 / g-140m 2 / g, which is measured using nitrogen and the BET method according to ISO 9277:2010, and the weight ratio of calcite to hydroxyapatite is 60:40-40:60, based on the dry weight of calcite and the dry weight of hydroxyapatite, and the titanium substance is present in an amount of 0.5-5% by weight of titanium element, based on the total dry weight of the surface-reacted calcium carbonate.

[0253] The white UV-absorbing titanium-doped surface-reacted calcium carbonate obtainable by the process of the present invention can be provided in the form of a suspension of white UV-absorbing titanium-doped surface-reacted calcium carbonate, as white UV-absorbing titanium-doped surface-reacted calcium carbonate alone or as dried white UV-absorbing titanium-doped surface-reacted calcium carbonate. According to a preferred embodiment, the white UV-absorbing titanium-doped surface-reacted calcium carbonate is a dried white UV-absorbing titanium-doped surface-reacted calcium carbonate.

[0254] If the white UV-absorbing titanium-doped surface-reacted calcium carbonate is dried, the moisture content of the dried white UV-absorbing titanium-doped surface-reacted calcium carbonate is less than or equal to 1.0 wt. %, preferably less than or equal to 0.5 wt. %, and more preferably less than or equal to 0.2 wt. %, based on the total weight of the dried white UV-absorbing titanium-doped surface-reacted calcium carbonate. According to another embodiment, the moisture content of the dried white UV-absorbing titanium-doped surface-reacted calcium carbonate is between 0.01 and 0.15 wt. %, preferably between 0.02 and 0.10 wt. % and more preferably between 0.03 and 0.07 wt. %, based on the total weight of the dried white UV-absorbing titanium-doped surface-reacted calcium carbonate.

[0255] The white UV-absorbing titanium-doped surface-reacted calcium carbonate of the present invention may also be provided and / or used in the form of a composition. According to one aspect of the present invention, a composition comprising the white UV-absorbing titanium-doped surface-reacted calcium carbonate of the present invention is provided. The composition may further comprise an additional surface-reacted calcium carbonate, wherein the additional surface-reacted calcium carbonate is a natural ground calcium carbonate or a precipitated calcium carbonate and at least one H3O + ion donor. Additionally or alternatively, other filler materials such as natural ground calcium carbonate, precipitated calcium carbonate and mixtures thereof may be present. The composition may comprise the white UV-absorbing surface-reacted calcium carbonate doped with titanium species according to the present invention in an amount of at least 20 wt. %, preferably at least 40 wt. %, more preferably at least 60 wt. % and most preferably at least 80 wt. %, based on the total weight of the composition.

[0256] The inventors have surprisingly discovered that the surface-reacted calcium carbonate formed by the process of the present invention provides additional functionality due to doping the surface-reacted calcium carbonate with a titanium-containing species.

[0257] For example, the inventors of the present invention have found that surface-reacted calcium carbonate doped with titanium species absorbs at least some of the UV radiation in the range of 280-400 nm. Therefore, the surface-reacted calcium carbonate of the present invention can be used for sun protection of plants and their parts or for chemical and physical sun protection in cosmetic preparations.

[0258] Furthermore, the inventors of the present invention have found that the surface-reacted calcium carbonate doped with titanium species is white and can therefore be used in suspensions, dispersions or slurries of minerals, fillers or pigments, which are typically used in polymer applications, paper coating applications, papermaking, especially in the manufacture of decorative paper, paints, coatings, sealants, adhesives, feed, pharmaceuticals, concrete, cement, cosmetics, water treatment, engineered wood applications, gypsum board applications, packaging applications, catalysis, gas treatment applications and / or agricultural applications and provide a white appearance without the addition of additional pigments.

[0259] Furthermore, the inventors surprisingly found that the white UV absorbing surface-reacted calcium carbonate doped with titanium species has a defined ratio of calcite to hydroxyapatite. In addition, it was found that the titanium species cannot be separated from the surface-reacted calcium carbonate by washing alone or in a liquid composition due to doping.

[0260] Furthermore, the inventors surprisingly found that white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species has a high surface area, which is an essential prerequisite for several applications.

[0261] Since the white, UV-absorbing, surface-reacted calcium carbonate is doped with titanium species, titanium dioxide particles in the submicron and / or nanometer size range do not have to be labeled in ingredient lists and should therefore have a higher acceptance by the end consumer.

[0262] Use of white UV absorbing titanium doped surface reacted calcium carbonate

[0263] White, UV absorbing, surface-reacted calcium carbonate doped with titanium species can be used in a variety of applications.

[0264] According to one embodiment, the white UV-absorbing surface-reacted calcium carbonate doped with titanium species according to the present invention or a composition comprising the same is used in polymer applications, paper coating applications, papermaking, especially in the manufacture of decorative paper, paints, coatings, sealants, adhesives, feed, pharmaceuticals, concrete, cement, cosmetics, water treatment, engineered wood applications, gypsum board applications, packaging applications, catalysis, gas treatment applications and / or agricultural applications. The engineered wood application may be included in an engineered wood product such as a wood composite, preferably a medium density fiberboard or a particleboard.

[0265] According to another embodiment of the invention, the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium substances according to the invention or a composition comprising it is used for sun protection of plants and parts thereof or for chemical and physical sun protection in cosmetic preparations.

[0266] The inventors have surprisingly found that such white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species or compositions comprising the same provide adequate sun protection for living cells, and in particular for human skin.

[0267] According to one embodiment of the invention, the cosmetic preparation is a sun protection product, a facial makeup, a hair care product, a hand care product, a skin care product, a body care product and mixtures thereof.

[0268] The surface-reacted calcium carbonate of the present invention may be incorporated into an article in order to provide an article with enhanced white color and / or enhanced UV absorption properties. According to a further aspect of the present invention, an article comprising the surface-reacted calcium carbonate obtainable by the process according to the present invention or a composition comprising the same is provided, wherein the article is selected from paper products, engineered wood products, gypsum board products, polymer products, hygiene products, medical products, health products, filtration products, woven materials, nonwoven materials, geotextile products, agricultural products, horticultural products, clothing, footwear products, luggage products, household products, industrial products, packaging products, building products and construction products.

[0269] The inventors have found in particular that the white UV-absorbing, surface-reacted calcium carbonate doped with titanium species of the present invention can be used in paper applications, in particular papermaking, such as making decorative paper. It has been found that a portion of the titanium dioxide in the decorative paper, which is quite expensive, can be replaced by the white UV-absorbing, surface-reacted calcium carbonate doped with titanium species of the present invention and the decorative paper still has improved optical properties such as improved opacity, improved brightness Ry and improved whiteness L*.

[0270] Attached photos:

[0271] Figure 1 : UV-visible spectra of samples 1 to 8 and GCC measured at 340 nm at room temperature

[0272] Figure 2 Show the SEM image of sample 4.

[0273] The scope and concerns of the present invention will be better understood based on the following examples, which are intended to illustrate some embodiments of the present invention and are non - restrictive.

[0274] Example section

[0275] 1. Measurement method

[0276] The following measurement methods are used to evaluate the parameters given in the examples and claims.

[0277] BET specific surface area (SSA) of the material

[0278] The BET specific surface area is measured via the BET method according to ISO 9277:2010 using nitrogen and an ASAP 2460 instrument (Micromeritics GmbH, Germany), and then conditioning the sample by heating for a period of 30 minutes at 100 °C. Before such measurement, the sample is filtered, rinsed and dried in an oven at 110 °C for at least 12 hours.

[0279] Particle size distribution of granular materials (% volume of particles with diameter < X), d 50 Value (volume median grain diameter) and d 98 Value:

[0280] The volume median particle diameter d 50 is evaluated using a Malvern Mastersizer 3000 laser diffraction system. The d 50 or d 98 values indicate the diameter values such that 50% or 98% of the particles, respectively, have a diameter less than this value by volume. The raw data obtained by the measurement is analyzed using Mie theory, where the particle refractive index is 1.57 and the absorption rate is 0.005.

[0281] The weight median particle diameter is determined by a sedimentation method, which is an analysis of the sedimentation behavior in a gravitational field. The measurement is carried out using a Sedigraph TM 5120, Micromeritics Instrument Corporation. The method and instrument are known to those skilled in the art and are commonly used for determining the grain size of fillers and pigments. The measurement is carried out in an aqueous solution of 0.1 wt% Na4P2O7. The sample is dispersed using a high - speed stirrer and ultrasonicated.

[0282] Methods and instruments are known to the skilled person and are commonly used for determining the crystallite size of fillers and pigments.

[0283] Porosity measurement

[0284] The titania or the white UV absorbing surface reacted calcium carbonate doped with titanium species were characterized by mercury porosimetry of porosity, intrusion total specific void volume and pore size distribution using a Micromeritics Autopore V 9620 mercury intrusion porosimeter. The maximum applied pressure of mercury was 414 MPa, equivalent to a Laplace throat diameter of 0.004 μm. The equilibrium time used at each pressure step was 20 s and the sample material was sealed in a 3 cm 3 The data were corrected for mercury compression and penetrometer effects and for elastic sample compression using Pore-Comp (PAC Gane et al. "Void Space Structure of Compressible Polymer Spheres and Consolidated Calcium Carbonate Paper-Coating Formulations" (Industrial and Engineering Chemistry Research 1996, 35 (5), 1753-1764). By taking the first derivative of the cumulative intrusion curve, the pore size distribution based on the equivalent Laplace diameter is revealed, which inevitably includes pore shielding. The volume-defined median pore size is calculated from the mercury intrusion curve, and the volume-defined pore size polydispersity is calculated from the pore size distribution curve as the full width at half maximum (FWHM).

[0285] X-ray diffraction (XRD)

[0286] XRD experiments were performed using a rotatable PMMA holder ring on the sample. The samples were analyzed using a Bruker D8 advanced powder diffractometer following the Bragg principle. This diffractometer contains a 2.2kW X-ray tube, sample holder, θ-θ-goniometer and detector. Nickel-filtered Cu-Kα radiation was used in all experiments. The graphs were automatically recorded in 2θ (XRD GV_7600) using a scan rate of 0.7° / min. The obtained powder diffraction patterns were classified by mineral content using the DIFFRACS suite software packages EVA and SEARCH based on reference patterns from the ICDD PDF-2 database (XRDLTM_7603).

[0287] Quantitative analysis of diffraction data refers to the determination of the amounts of different phases in a multiphase sample and has been performed using the DIFFRAC suite software package TOPAS. In detail, quantitative analysis allows the determination of structural properties and phase ratios with quantifiable numerical accuracy from the experimental data itself. This involves modeling the full diffraction pattern using the Rietveld method so that the calculated pattern(s) replicate the experimental pattern.

[0288] Reflectivity measurement

[0289] Reflectance analysis was performed using a dual beam PerkinElmer Lambda 950 UV / Visible / NIR spectrophotometer equipped with a 150 mm integrating sphere with a PMT and InGaAs detector.

[0290] The prepared dry composition was measured by reflectance spectroscopy. The dry composition was analyzed by placing it in a sealed aluminum cup for powder samples flush with the reflectance port of the integrating sphere. The spectrophotometer was scanned in the range of 280nm-800nm ​​with a step size of 2nm. The Spectralon white standard was used as a 100% baseline. To obtain a surrogate of the absorbance spectrum of the dry composition, the Kubelka-Munk equation KM=K / S=(1-R) ​​was used. 2 / 2R transforms the measured reflectance spectrum, where R is the reflectance and K and S are the absorption and scattering coefficients, respectively.

[0291] (XRF) Measurement

[0292] 11.5 g of the dried sample was pressed into tablets using a press at 400 kN. TM The elemental composition of the samples was measured using a PERFORM'X X-ray fluorescence spectrometer (Thermo Fisher Scientific, Inc., USA). Quantification was performed using an external calibration specifically prepared for calcium carbonate.

[0293] Brightness Ry and paper opacity

[0294] Brightness Ry and decorative paper opacity were measured on the resulting decorative paper prepared as follows on white and black substrates. The decorative paper was stored at 23±1° C. and 50±2% relative humidity for 24 h and thereafter measured at the same temperature and humidity. The measurements were carried out with an Elrepho-spectrophotometer 3300ERIC (Lorentzen & Wettre) according to ISO 2471:2008-12. A measuring aperture XLAV (34 mm diameter), a D65 / 10° illuminant and an R457 filter were used.

[0295] The opacity is calculated from the quotient of the average value of the reflectance Ry of the black background and the average value of the reflectance Ry of the white background, and is expressed in %.

[0296] CIELAB coordinates

[0297] The color values ​​(CIELAB L*, a*, b* coordinates) were measured on the resulting decorative paper prepared as follows on a white and black substrate. The decorative paper was stored at 23±1°C and 50±2% relative humidity for 24 h and thereafter measured at the same temperature and humidity. The measurements were carried out with an Elrepho-spectrophotometer 3300ERIC (Lorentzen & Wettre) according to ISO 5631-2:2015-11 (light D65). A measuring aperture XLAV (diameter 34 mm) was used.

[0298] 2. Materials and Equipment

[0299] Materials containing calcium carbonate:

[0300] GCCI: Ground marble calcium carbonate from Carrera, Italy. The ground calcium carbonate has a median particle size distribution based on weight. 50 7.9 μm, as determined by sedimentation.

[0301] GCCII: Ground marble calcium carbonate from Hustadmarmor, Norway. The ground calcium carbonate has a median particle size distribution based on weight. 50 1.7 μm, as determined by sedimentation.

[0302] H3O + Ion donor:

[0303] Phosphoric acid (H3PO4), available from VWR Chemicals (orthophosphoric acid ≥ 85%)

[0304] Substances containing titanium:

[0305] Titanyl sulfate / TiOSO4×H2O, available from Sigma-Aldrich as serial number 14023-1

[0306] Titanium Dioxide:

[0307] Non-porous titanium dioxide with a specific surface area (SSA) of 6.8 m 2 / g and weight-based median particle size distribution d 50 1.7 μm, as determined by sedimentation.

[0308] Wet Enhancer:

[0309] ·Solution of adipate-diethylenetriamine-epichlorohydrin copolymer ( XP 14, BK Giulini GmbH

[0310] 3. Sample Preparation

[0311] White UV absorbing titanium doped surface reacted calcium carbonate I

[0312] 165 g of GCCI was added to 940 mL of water. The slurry was mixed at 75° C. for 15 minutes. The resulting mixture was referred to as GCCI slurry.

[0313] A H3PO4 solution (Solution A) was prepared by using 58 g of phosphoric acid in 107 mL of distilled water. Solution A was added to the GCCI slurry at a flow rate of 15 g / min, with a complete addition time of approximately 10 minutes.

[0314] For 2.5 wt% titanium, 13.6 g of the titanium containing material were added to 1.1 L of water. The salt addition was performed batchwise and under stirring.

[0315] Thereafter, the solvent was removed by solvent evaporation (in an oven at 100° C. overnight) or pressure filtration (vacuum filtration—water pump vacuum at room temperature).

[0316] Different inventive and comparative experiments were performed as listed below. Each sample was dried at 125°C and 300°C.

[0317]

[0318]

[0319] The obtained samples were analyzed using UV-visible spectroscopy. Figure 1 The total reflectance of the sample at 340 nm was measured at room temperature.

[0320] White UV absorbing titanium doped surface reacted calcium carbonate II

[0321] GCCI I slurry preparation

[0322] 7 liters of an aqueous suspension of ground calcium carbonate was prepared in a mixing vessel by adjusting the solids content of GCCI I so as to obtain a solids content of 14 wt.-%, based on the total weight of the aqueous suspension. The slurry was mixed at 70°C for 15 minutes.

[0323] Sample 8

[0324] While the GCCI I slurry was mixing, 1391 g of 23 wt% phosphoric acid was added over 60 minutes. Throughout the addition, the temperature of the suspension was maintained at 70° C. + / - 1° C. After the addition of the phosphoric acid, the suspension was stirred for an additional 5 minutes before being removed from the vessel and allowed to cool.

[0325] Sample 9

[0326] Separately, a solution of a titanium-containing substance was prepared by slowly adding the titanium-containing substance dissolved in deionized water to phosphoric acid to give a final concentration of 40.5 wt % H3PO4 and 6.9 wt % TiOSO4 x H2 O. This solution was then diluted with more distilled water to give a concentration of 23 wt % H3PO4.

[0327] While the GCCI I slurry was mixed, 1075 g of the titanium containing material solution was added over 60 minutes. Throughout the addition, the temperature of the resulting mixture was maintained at 70° C. + / - 1° C. The resulting mixture was then stirred for an additional 5 minutes before being removed from the container and allowed to cool.

[0328] Sample 10

[0329] Separately, a solution of a titanium-containing substance was prepared in phosphoric acid by slowly adding the titanium-containing substance dissolved in deionized water to a final concentration of 40.5 wt % H3PO4 and 6.9 wt % TiOSO4 x H2 O. This solution was then diluted with more distilled water to give a concentration of 23 wt % H3PO4.

[0330] While the GCCI I slurry was mixing, 2093 g of the titanium containing material solution was added over 60 minutes. Throughout the addition, the temperature of the resulting mixture was maintained at 70° C. + / - 1° C. The resulting mixture was then stirred for an additional 5 minutes before being removed from the vessel and allowed to cool.

[0331] Thereafter, the solvent in the resulting mixture was removed by pressure filtration through a Buchner funnel in a water pump vacuum. Each sample was dried at 125° C. The obtained samples were analyzed using UV-visible spectroscopy. The total reflectance of the samples at 340 nm was measured at room temperature.

[0332] from Figure 1 It can be seen that the comparative sample 6 has a total reflectivity similar to that of the original GCCI. When comparing sample 6 with samples 1 to 4, it can be seen that these samples have much lower total reflectivity values ​​between 62 and 77%. Thus, it has been shown that it is possible to add at least one substance containing titanium before and / or during and / or after step d) (samples 1 to 3). In addition, solvent removal has no effect on the obtained white UV-absorbing surface-reacted calcium carbonate doped with titanium species, which can be seen from samples 1 and 3.

[0333] It can be seen that comparative sample 8 has a total reflectivity of 93.79%. When comparing sample 8 with samples 9 and 10, it can be seen that these samples have much lower total reflectivity values ​​between 86 and 90%. Thus, a white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species can be prepared by the method of the present invention.

[0334] Sample 8 Sample 9 Sample 10 Reflectivity at 340nm in % 93.79 89.39 86.53

[0335] Samples 1 to 10 were analyzed by XRD and XRF and the surface area was additionally evaluated using the BET technique.

[0336]

[0337] It can be seen from samples 1 to 4 and 9 and 10 that a white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species can be prepared by the inventive method of the present invention.

[0338] It can be seen from sample 5 that without adding H3O + In the case of ion donors, no hydroxyapatite was formed. In addition, the BET value was below 15 m 2 / g.

[0339] It can be seen from Samples 6 and 8 that, without adding a substance containing titanium, titanium is not present.

[0340] As can be seen from Sample 7, by mixing only the surface-reacted calcium carbonate and the substance containing titanium, the BET value was 12 m / s. 2 / g, and is therefore lower than the value for the claimed white UV-absorbing surface-reacted calcium carbonate doped with titanium species. Without being bound by any theory, the inventors believe that by mixing only the surface-reacted calcium carbonate and the titanium-containing species, the pores on the surface are blocked.

[0341] In addition, a SEM photograph was taken from Sample 4. It can be seen that due to the use of at least one H3O + The material comprising calcium carbonate is treated with an ion donor and at least one substance comprising titanium to obtain a white, UV absorbing, surface-reacted calcium carbonate doped with a titanium substance having a unique structure with a high surface area, wherein the pores of the obtained product are not blocked.

[0342] Thus, the example shows that by the inventive method of the present invention, a white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species can be prepared, which comprises calcite and hydroxyapatite and has a specific surface area of ​​15 m 2 / g-200m 2 / g, measured using nitrogen and the BET method according to ISO 9277:2010, wherein the weight ratio of calcite to hydroxyapatite is 99:1-1:99 based on the dry weight of calcite and the dry weight of hydroxyapatite, and wherein the titanium species is present in an amount of 0.01-20 wt% titanium element, based on the total dry weight of the surface-reacted calcium carbonate.

[0343] In addition, the samples were analyzed for d 50 and the specific pore volume of the particle intrusion.

[0344]

[0345]

[0346] Preparation and testing of decorative papers

[0347] Different decorative papers were prepared as follows:

[0348] 80 g of oven-dried (German term "otro" or "Ofentrocken") eucalyptus standard pulp with a Schopper Riegler degree of 30° SR and 4.5 g of a wet strength agent were mixed at 10 dm 3 The suspension was diluted in tap water. Thereafter, the fillers were added in the amounts indicated in the following table. The resulting suspension was stirred for 10 minutes with a paddle mixer. Manual sheet forming machine forms 15 80g / m 2 Each sheet was wet pressed and The dryer was dried at 115° C. The composition of the decorative paper is given in the table below.

[0349]

[0350] *The sum of fibers / pulp and fillers always accounts for 100 parts by weight. Wet strength agents are added in addition to the 100 parts by weight.

[0351]

[0352]

[0353] From the above measurement results, it can be seen that the white UV-absorbing surface-reacted calcium carbonate doped with titanium species of the present invention can be used in paper applications, especially papermaking, such as making decorative paper. Samples 12 and 13 show improved opacity, improved brightness Ry and improved whiteness L* compared to sample 11, even though less TiO2 is present in these decorative papers.

[0354] Thus, a portion of the titanium dioxide in the decorative paper, which is a high-priced product, can be replaced by the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species of the present invention and the decorative paper still has improved properties such as improved opacity, improved brightness Ry and improved whiteness L*.

Claims

1. A method for producing white UV absorbing titanium-doped surface-reacted calcium carbonate comprising the following steps: a) providing a material comprising calcium carbonate, b) Provide at least one H3O + ion donor, c) providing at least one substance comprising titanium, and d) treating in an aqueous medium with the at least one H3O + treating the calcium carbonate-containing material of step a) with an ion donor to form an aqueous suspension of surface-reacted calcium carbonate, and wherein the at least one substance comprising titanium of step c) is added before and / or during and / or after step d).

2. The method according to claim 1, wherein the material comprising calcium carbonate is natural ground calcium carbonate and / or precipitated calcium carbonate, preferably the natural ground calcium carbonate is selected from marble, chalk, limestone and mixtures thereof, and / or the precipitated calcium carbonate is selected from precipitated calcium carbonate having aragonite, vaterite or calcite crystal form and mixtures thereof.

3. The method according to claim 1 or 2, wherein the calcium carbonate containing material is in the form of particles having a weight median particle size d of 0.05-10 μm, preferably 0.2-5.0 μm, more preferably 0.4-3.0 μm and most preferably 0.6-1.2 μm. 50 (by weight), and / or a weight top cut particle size d of 0.15-55 μm, preferably 1-40 μm, more preferably 2-25 μm and most preferably 3-15 μm 98 (weight).

4. The method according to any one of the preceding claims, wherein the at least one H3O + The ion donor is selected from phosphoric acid, citric acid, acid salts, tartaric acid and mixtures thereof, preferably the at least one H3O + The ion donor is selected from phosphoric acid, Li + 、Na + and / or K + The cations are at least partially neutralized by H2PO4 - , by selecting Li + 、Na + , K + Mg 2+ and / or Ca 2+ The cation is at least partially neutralized by HPO4 2- , citric acid and mixtures thereof, more preferably at least one H3O + The ion donor is selected from phosphoric acid, citric acid or a mixture thereof, and most preferably the at least one H3O + The ion donor is phosphoric acid.

5. The method according to any one of the preceding claims, wherein the at least one H3O + The molar ratio of ion donor to the material comprising calcium carbonate is 0.01-4, preferably 0.02-2, more preferably 0.05-1 and most preferably 0.1-0.

58.

6. The method according to any one of the preceding claims, wherein the at least one titanium-containing substance is selected from titanium salts, titanium hydroxide, titanium dioxide and mixtures thereof, preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof.

7. The method according to any one of the preceding claims, wherein the at least one substance comprising titanium is provided in an amount of 0.1-20 wt.% of the element titanium, based on the total dry weight of the material comprising calcium carbonate, preferably 0.5-15 wt.%, more preferably 1.0-10 wt.% and most preferably 2.5-7.5 wt.%.

8. The method according to any one of the preceding claims, wherein in step d), the material comprising calcium carbonate is treated with the at least one H3O + Solution treatment of the ion donor and the at least one titanium-containing substance of step c).

9. The process according to any one of the preceding claims, wherein in step d), the pH value of the aqueous suspension of surface-reacted calcium carbonate obtained is 4.5-11, preferably 5.5-10 and most preferably 6.0-8.

0.

10. The process according to any one of the preceding claims, wherein step d) is carried out at a temperature of 20-95°C, preferably 30-85°C, more preferably 40-80°C, even more preferably 50-75°C and most preferably 65-73°C.

11. The method according to any one of the preceding claims, wherein the method further comprises a step e) of separating the white UV absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step d), and preferably step e) is performed by solvent evaporation and / or filter pressing, and / or The method further comprises the step f) of drying the surface-reacted calcium carbonate doped with titanium species at a temperature in the range of 60-600° C., preferably 80-450° C., most preferably 95-400° C., after step d) or after step e) if present, preferably until the moisture content of the surface-reacted calcium carbonate doped with titanium species is less than 1 wt.-%, based on the total weight of the dried surface-reacted calcium carbonate.

12. White UV absorbing titanium doped surface reacted calcium carbonate containing calcite and hydroxyapatite and having 15 m 2 / g-200m 2 The specific surface area of ​​​​the nanostructured carbon foam is 2.5477 g, which is measured using nitrogen and the BET method according to ISO 9277:2010, wherein the weight ratio of calcite to hydroxyapatite is from 99:1 to 1:99, based on the dry weight of the calcite and the dry weight of the hydroxyapatite, and The titanium substance is present in an amount of 0.01-20 wt % of titanium element, based on the total dry weight of the surface-reacted calcium carbonate.

13. The surface-reacted calcium carbonate doped with titanium species according to claim 12, wherein the surface-reacted calcium carbonate doped with titanium species has (i)25m 2 / g-180m 2 / g, more preferably 30m 2 / g-160m 2 / g, even more preferably 45m 2 / g-150m 2 / g, most preferably 50m 2 / g-140m 2 Specific surface area of ​​100 g / m, measured using nitrogen and the BET method according to ISO 9277:2010, and / or (ii) a volume-determined median particle size d of 1-100 μm, preferably 2-60 μm, more preferably 3-40 μm, even more preferably 4-30 μm and most preferably 5-15 μm 50 (volume), and / or (iii) a volume-determined top cut particle size d of 2-150 μm, preferably 4-100 μm, more preferably 6-80 μm, even more preferably 8-60 μm and most preferably 10-30 μm 98 (volume), and / or (iv) 0.1-2.3 cm 3 / g, preferably 0.2-2.0cm 3 / g, more preferably 0.4-1.8cm 3 / g and most preferably 0.6-1.6cm 3 The intrusion specific pore volume in the particle range of / g was calculated from the results of mercury porosimetry measurements.

14. The surface-reacted calcium carbonate doped with titanium species according to claim 12 or 13, wherein the weight ratio of calcite to hydroxyapatite is from 80:20 to 20:80, preferably from 70:30 to 30:70 and most preferably from 60:40 to 40:60, based on the dry weight of the calcite and the dry weight of the hydroxyapatite, and / or The titanium species is present in an amount of 0.05-15 wt% titanium element, based on the total dry weight of the surface-reacted calcium carbonate, preferably 0.1-10 wt% and most preferably 0.5-5 wt%.

15. Use of the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species according to any one of claims 12 to 14 in polymer applications, paper coating applications, papermaking, in particular in the manufacture of decorative paper, paints, coatings, sealants, adhesives, feed, pharmaceuticals, concrete, cement, cosmetics, water treatment, engineered wood applications, gypsum board applications, packaging applications, catalysis, gas treatment applications and / or agricultural applications.

16. Use of the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium substances according to any one of claims 12 to 14 for sun protection of plants and parts thereof or for chemical and physical sun protection in cosmetic preparations.

17. An article comprising the white, UV absorbing, surface-reacted calcium carbonate doped with titanium species according to any one of claims 12 to 14, wherein the article is selected from the group consisting of paper products, engineered wood products, gypsum board products, polymer products, hygiene products, medical products, health products, filtration products, woven materials, nonwoven materials, geotextile products, agricultural products, horticultural products, clothing, footwear products, luggage products, household products, industrial products, packaging products, building products and construction products.

Citation Information

Patent Citations

  • Coating composition deposited on a substrate containing microparticles of TiO2

    EP0634462A2

  • Precipitated calcium carbonate pigment, especially for use in inkjet printing paper coatings

    EP1712523A1

  • Process for preparing precipitated calcium carbonate pigment, especially for use in inkjet printing pater coatings and precipitated calcium carbonate

    EP1712597A1

  • Photocatalytic coating

    EP2188125A1

  • Process to prepare a surface-reacted calcium carbonate implementing a weak acid, resulting products and uses thereof

    EP2264108A1